Resin composition
The resin composition with a balanced liquid epoxy resin and carbon-containing inorganic filler addresses non-uniformity and insulation issues in circuit boards and semiconductor chip packages, achieving stable, high-reliability insulating layers with enhanced fluidity and heat resistance.
Patent Information
- Application Number
- JP2024516125
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-04-18
- Filing Date
- 2023-03-08
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-03-08
AI Technical Summary
Circuit boards and semiconductor chip packages face challenges with non-uniform thickness and reduced insulation reliability due to low-viscosity resin compositions, which lead to uneven thickness and instability in insulating layers, especially in large formats with high wiring density and increased communication speeds.
A resin composition comprising a specific range of liquid epoxy resin and carbon-containing inorganic filler, such as silica particles, to achieve both excellent fluidity and insulation reliability, with a carbon content of 0.1% to 5% by mass, and a mass ratio of carbon-containing inorganic filler to epoxy resin of 0.5 to 200, enhancing the cured product's properties.
The resin composition provides a cured product with improved fluidity, insulation reliability, and heat resistance, ensuring uniform thickness and stability of insulating layers, reducing the risk of conductor layer peeling and enhancing reflow resistance.
Smart Images

Figure 0007616484000004 
Figure 0007616484000001 
Figure 0007616484000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition. The present invention also relates to a cured product, a sheet-like laminate material, a resin sheet, a circuit board, a semiconductor chip package, and a semiconductor device using the resin composition. [Background technology]
[0002] In general, an insulating layer is provided on a circuit board and a semiconductor chip package. For example, an interlayer insulating layer may be provided as an insulating layer on a printed wiring board, which is a type of circuit board. Also, for example, a rewiring formation layer may be provided as an insulating layer on a semiconductor chip package. These insulating layers may be formed from a cured product obtained by curing a resin composition (Patent Documents 1-2). Furthermore, the technology disclosed in Patent Document 3 is known. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 3644761 [Patent Document 2] International Publication No. 2019 / 216388 [Patent Document 3] JP 2020-37643 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, circuit boards and semiconductor chip packages have become larger, wiring has become denser, and communication has become faster. In order to properly embed fine wiring formed at high density with a resin composition, the resin composition is required to have high fluidity. In order to achieve high fluidity, it is possible to reduce the viscosity of the resin composition. However, when the viscosity of the resin composition is reduced, the resin composition flows when embedding wiring with the resin composition, and the stability of the thickness of the insulating layer obtained by curing the resin composition may be reduced. For example, when wiring formed on the surface of a substrate is embedded with a resin composition, the thickness of the resin composition may differ between the part on the wiring and the gap part between the wiring, resulting in an uneven thickness of the insulating layer. In particular, in large circuit boards and semiconductor chip packages, the area of the insulating layer is large, so it is difficult to stably and uniformly make the thickness of the insulating layer throughout the entire insulating layer.
[0005] In addition, due to the increase in size of circuit boards and semiconductor chip packages, the increase in wiring density, and the progress of high-speed communication, the level of insulation reliability required for insulating layers has been increasing in recent years. However, when a low-viscosity epoxy resin is used to reduce the viscosity of a resin composition, the insulation reliability tends to be low because the low-viscosity epoxy resin generally contains a large amount of chlorine.
[0006] The present invention has been devised in view of the above-mentioned problems, and has an object to provide a resin composition which can give a cured product having excellent insulation reliability and excellent flowability; a cured product of the resin composition; a sheet-like laminate material and a resin sheet which contain the resin composition; and a circuit board, a semiconductor chip package, and a semiconductor device which contain the cured product. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above-mentioned problems, and as a result, have found that a resin composition containing in combination an epoxy resin (A) containing a liquid epoxy resin (A-1) in a specific range of amount and an inorganic filler (B) containing a carbon-containing inorganic filler (B-1) in a specific range of amount can solve the above-mentioned problems, thereby completing the present invention. That is, the present invention includes the following.
[0008] [1] A resin composition comprising (A) an epoxy resin and (B) an inorganic filler, (A) the epoxy resin contains (A-1) a liquid epoxy resin, (B) the inorganic filler contains (B-1) a carbon-containing inorganic filler having a carbon content of 0.1 mass% or more, The amount of the liquid epoxy resin (A-1) is 0.5% by mass or more based on 100% by mass of the non-volatile components of the resin composition; (B-1) A resin composition, in which the amount of a carbon-containing inorganic filler is 10% by mass or more relative to 100% by mass of the non-volatile components of the resin composition. [2] The resin composition according to [1], further comprising a curing agent (C). [3] The resin composition according to [1] or [2], wherein the amount of the carbon-containing inorganic filler (B-1) is 20 mass% or more relative to 100 mass% of the total amount of the inorganic filler (B). [4] The resin composition according to any one of [1] to [3], wherein the carbon-containing inorganic filler (B-1) is silica particles having a carbon content of 0.2 mass % or more. [5] The resin composition according to any one of [1] to [4], wherein the carbon content of the carbon-containing inorganic filler (B-1) is 5 mass % or less. [6] The resin composition according to any one of [1] to [5], wherein the liquid epoxy resin (A-1) has a weight average molecular weight of 1,000 or less. [7] The resin composition according to any one of [1] to [6], wherein the liquid epoxy resin (A-1) is a non-aromatic epoxy resin. [8] The resin composition according to any one of [1] to [7], wherein the liquid epoxy resin (A-1) has a viscosity of 15,000 mPa s or less at 25°C. [9] The resin composition according to any one of [1] to [8], further comprising (D) a curing accelerator.
[10] The resin composition according to any one of [1] to [9], further comprising a thermoplastic resin (E).
[11] The resin composition according to any one of [1] to
[10] , which has a minimum melt viscosity of less than 4,000 poise.
[12] When a resin composition is thermally cured at 190°C for 90 minutes to obtain a cured product, and a voltage of 3.3 V is applied to the cured product at 130°C and 85% RH for 100 hours, the insulation resistance of the cured product measured using a comb-shaped electrode with a line / space of 15 μm / 15 μm is 1.0 × 10 8 The resin composition according to any one of [1] to
[11] , having a hardness of Ω or more.
[13] The resin composition according to any one of [1] to
[12] , which is for forming an insulating layer.
[14] A cured product of the resin composition described in any one of [1] to
[13] .
[15] A sheet-like laminate material comprising the resin composition according to any one of [1] to
[13] .
[16] A support and a resin composition layer formed on the support, A resin sheet, wherein a resin composition layer contains the resin composition according to any one of [1] to
[13] .
[17] A circuit board comprising a cured product of the resin composition according to any one of [1] to
[13] .
[18] A semiconductor chip package comprising a cured product of the resin composition described in any one of [1] to
[13] .
[19] A semiconductor device comprising the circuit board according to
[17] .
[20] A semiconductor device comprising the semiconductor chip package described in
[18] . Effect of the Invention
[0009] According to the present invention, it is possible to provide a resin composition which can give a cured product having excellent insulation reliability and excellent flowability; a cured product of the resin composition; a sheet-like laminate material and a resin sheet which contain the resin composition; and a circuit board, a semiconductor chip package, and a semiconductor device which contain the cured product. [Brief description of the drawings]
[0010] [Figure 1]FIG. 1 is a cross-sectional view showing a schematic diagram of a fan-out type WLP as an example of a semiconductor chip package according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the present invention will be described with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and may be modified as desired without departing from the scope of the claims and their equivalents.
[0012] In the following description, the term "(meth)acrylic acid" includes acrylic acid, methacrylic acid, and combinations thereof, and the term "(meth)acrylate" includes acrylate, methacrylate, and combinations thereof.
[0013] In the following description, the term "dielectric constant" refers to the relative dielectric constant unless otherwise specified.
[0014] [Resin composition overview] A resin composition according to one embodiment of the present invention contains an epoxy resin (A) and an inorganic filler (B). The epoxy resin (A) contains a liquid epoxy resin (A-1) in a specific range of amount. The inorganic filler (B) contains a carbon-containing inorganic filler (B-1) in a specific range of amount. Here, the carbon-containing inorganic filler (B-1) refers to an inorganic filler containing carbon in a specific range of amount.
[0015] The resin composition according to one embodiment of the present invention can have excellent fluidity. In addition, according to the resin composition according to one embodiment of the present invention, a cured product having excellent insulation reliability can be obtained. Therefore, according to the resin composition according to one embodiment of the present invention, both fluidity and insulation reliability can be improved. Furthermore, the resin composition according to one embodiment of the present invention can usually have a low minimum melt viscosity. In addition, according to the resin composition according to one embodiment of the present invention, a cured product having excellent heat resistance can usually be obtained.
[0016] The present inventors speculate that the mechanism by which the resin composition according to one embodiment of the present invention provides the above-mentioned excellent effects is as follows, however, the scope of the present invention is not limited to the mechanism described below.
[0017] The resin composition according to one embodiment of the present invention contains a specific range of amount of liquid epoxy resin (A-1), and therefore can have a low viscosity. Therefore, excellent fluidity can be achieved. However, in general, low-viscosity liquid epoxy resin (A-1) tends to contain a large amount of chlorine due to its manufacturing method. Such compositions containing a large amount of chlorine usually have poor insulation reliability.
[0018] In contrast, the resin composition according to one embodiment of the present invention contains a specific range of the amount of (A-1) liquid epoxy resin in combination with a specific range of the amount of (B-1) carbon-containing inorganic filler. In such a resin composition, the carbon contained in the (B-1) carbon-containing inorganic filler can capture chlorine, so that the deterioration of insulation reliability caused by chlorine can be suppressed. Therefore, it is possible to achieve improvements in both fluidity and insulation reliability.
[0019] Another method for suppressing the deterioration of insulation reliability due to chlorine may be to introduce an ion catcher into the resin composition. However, since the ion catcher generally has poor affinity with the resin component in the resin composition, the resin composition containing the ion catcher has poor composition uniformity at a microscopic level. In addition, the ion catcher generally tends to have poor heat resistance. Therefore, the resin composition containing the conventional ion catcher has high viscosity as a whole composition, or has locally generated parts with poor fluidity and heat resistance, and as a result, the resin composition as a whole has poor fluidity and heat resistance. In contrast, in the resin composition according to one embodiment of the present invention, the carbon that captures chlorine does not reduce the affinity between the inorganic filler and the resin component or the heat resistance, and therefore, the carbon captures chlorine to increase the insulation reliability, while maintaining the heat resistance and fully exerting the effect of improving the fluidity of the liquid epoxy resin (A-1), thereby achieving improvements in both fluidity and insulation reliability.
[0020] Furthermore, the liquid epoxy resin (A-1) usually has a small molecular weight, and therefore tends to have a small epoxy equivalent. Therefore, a resin composition containing a specific range of the liquid epoxy resin (A-1) can form many crosslinking points formed by the reaction of epoxy groups during curing. Therefore, a dense network of crosslinked structures can be formed, and high heat resistance can be obtained. Therefore, for example, a cured product having a high glass transition temperature can be obtained.
[0021] Also, as described above, unlike the resin composition containing an ion catcher, the resin composition according to one embodiment of the present invention can have a high compositional uniformity. Therefore, the cured product can also have a high compositional uniformity, so that the occurrence of non-uniform points of the composition that are the starting point of destruction due to stress can be suppressed. Therefore, when a conductor layer is formed on an insulating layer containing a cured product of a resin composition, and the insulating layer is heated and stress occurs in the insulating layer, the destruction of the insulating layer due to the stress can be suppressed. Therefore, peeling of the conductor layer accompanied by destruction of the insulating layer can be suppressed, so that excellent reflow resistance can be obtained.
[0022] [(A) Epoxy resin] A resin composition according to one embodiment of the present invention contains an epoxy resin (A) as component (A). The epoxy resin (A) may be a curable resin having an epoxy group. Examples of the epoxy resin (A) include trimethylolpropane type epoxy resin, neopentyl glycol type epoxy resin, bixylenol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol novolac type epoxy resin, phenol novolac type epoxy resin, tert-butyl-catechol type epoxy resin, naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, glycerol type epoxy resin, and the like. Examples of the epoxy resin include diphenylamine type epoxy resin, glycidyl ester type epoxy resin, cresol novolac type epoxy resin, phenol aralkyl type epoxy resin, biphenyl type epoxy resin, linear aliphatic epoxy resin, epoxy resin having a butadiene structure, alicyclic epoxy resin, heterocyclic epoxy resin, spiro ring-containing epoxy resin, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, naphthylene ether type epoxy resin, trimethylol type epoxy resin, tetraphenylethane type epoxy resin, isocyanurate type epoxy resin, phenolphthalimidine type epoxy resin, etc. (A) The epoxy resin may be used alone or in combination of two or more kinds.
[0023] The (A) epoxy resin contains a specific amount of the (A-1) liquid epoxy resin. The (A-1) liquid epoxy resin refers to an epoxy resin that is liquid at a temperature of 20° C. The (A-1) liquid epoxy resin preferably has two or more epoxy groups in one molecule.
[0024] Examples of the (A-1) liquid epoxy resin include bisphenol A type liquid epoxy resin, bisphenol F type liquid epoxy resin, bisphenol AF type liquid epoxy resin, naphthalene type liquid epoxy resin, glycidyl ester type liquid epoxy resin, glycidyl amine type liquid epoxy resin, phenol novolac type liquid epoxy resin, trimethylolpropane type liquid epoxy resin, neopentyl glycol type liquid epoxy resin, alicyclic liquid epoxy resin having an ester skeleton, cyclohexane type liquid epoxy resin, cyclohexane dimethanol type liquid epoxy resin, and liquid epoxy resin having a butadiene structure. The (A-1) liquid epoxy resin may be used alone or in combination of two or more types.
[0025] The liquid epoxy resin (A-1) preferably contains a non-aromatic epoxy resin, and preferably contains only a non-aromatic epoxy resin. The non-aromatic epoxy resin refers to an epoxy resin that does not contain an aromatic ring in its molecule. The term "aromatic ring" refers to a ring that follows the Huckel rule, in which the number of electrons contained in the π-electron system on the ring is 4p+2 (p is an integer of 0 or more), and includes a monocyclic aromatic ring and a condensed polycyclic aromatic ring in which two or more monocyclic aromatic rings are condensed. The aromatic ring also includes an aromatic carbon ring and an aromatic heterocycle. Therefore, the non-aromatic epoxy resin is preferably an aliphatic epoxy resin. The non-aromatic epoxy resin may contain an alicyclic structure. When the liquid epoxy resin (A-1) containing a non-aromatic epoxy resin is used, the fluidity and insulation reliability can be effectively improved, and furthermore, the minimum melt viscosity and heat resistance can usually be particularly improved. Among the (A-1) liquid epoxy resins, examples of non-aromatic epoxy resins include trimethylolpropane type liquid epoxy resins, neopentyl glycol type liquid epoxy resins, hexanediol type liquid epoxy resins, polypropylene glycol type liquid epoxy resins, alicyclic liquid epoxy resins having an ester skeleton, cyclohexane type liquid epoxy resins, cyclohexanedimethanol type liquid epoxy resins, and liquid epoxy resins having a butadiene structure.
[0026] Specific examples of the (A-1) liquid epoxy resin include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type liquid epoxy resins) manufactured by DIC Corporation; "828US", "828EL", "jER828EL", "825", and "Epikote 828EL" (bisphenol A type liquid epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type liquid epoxy resins) manufactured by Mitsubishi Chemical Corporation; and "jER152" ( Phenol novolac type liquid epoxy resin; Mitsubishi Chemical's "630", "630LSD", and "604" (glycidylamine type liquid epoxy resin); ADEKA's "ED-523T" (glycirol type liquid epoxy resin); ADEKA's "EP-3950L", "EP-3980S" (glycidylamine type liquid epoxy resin); ADEKA's "EP-4088S" (dicyclopentadiene type liquid epoxy resin); Nippon Steel Chemical & Material's " ZX1059 (a mixture of bisphenol A type liquid epoxy resin and bisphenol F type liquid epoxy resin); EX-721 (glycidyl ester type liquid epoxy resin) manufactured by Nagase ChemteX; Celloxide 2021P (alicyclic liquid epoxy resin with ester structure) manufactured by Daicel; PB-3600 manufactured by Daicel, JP-100 and JP-200 (liquid epoxy resin with butadiene structure) manufactured by Nippon Steel Chemical & Material Examples of such liquid epoxy resins include "ZX1658" and "ZX1658GS" manufactured by Adeka Corporation (liquid 1,4-glycidylcyclohexane type liquid epoxy resins); "ED-503" and "ED-503G" manufactured by Adeka Corporation (hexanediol type liquid epoxy resins); "ED-505" manufactured by Adeka Corporation (trimethylolpropane type liquid epoxy resin); "ED-506" manufactured by Adeka Corporation (polypropylene glycol type liquid epoxy resin); and "ED-523T" manufactured by Adeka Corporation (neopentyl glycol type liquid epoxy resin).
[0027] It is preferable that the liquid epoxy resin (A-1) has a small weight-average molecular weight in a specific range. Specifically, the weight-average molecular weight of the liquid epoxy resin (A-1) is preferably 1000 or less, more preferably 500 or less, and even more preferably 300 or less. When the liquid epoxy resin (A-1) having a weight-average molecular weight in this range is used, the fluidity and insulation reliability can be effectively improved, and furthermore, the minimum melt viscosity and heat resistance can usually be particularly improved. The lower limit is not particularly limited, and can be, for example, 50 or more, 80 or more, 100 or more, etc. The weight-average molecular weight of the resin can be measured as a polystyrene-equivalent value by gel permeation chromatography (GPC).
[0028] The liquid epoxy resin (A-1) preferably has a small viscosity within a specific range. The viscosity range of the liquid epoxy resin (A-1) is preferably 15,000 mPa·s or less, more preferably 3,000 mPa·s or less, even more preferably 1,000 mPa or less, and particularly preferably 500 mPa·s or less. When the liquid epoxy resin (A-1) having a viscosity within this range is used, the fluidity and insulation reliability can be effectively improved, and furthermore, the minimum melt viscosity and heat resistance can usually be particularly improved. The lower limit is not particularly limited, and can be, for example, 5 mPa·s or more, 10 mPa·s or more, etc. The viscosity of the liquid epoxy resin can be measured using an E-type viscometer under conditions of 25°C and 20 rpm. A specific method for measuring the viscosity can be adopted as described in <Measurement of viscosity of epoxy resin> in the examples below.
[0029] As described above, the liquid epoxy resin (A-1) having a low viscosity may generally contain chlorine. The amount of chlorine contained in the liquid epoxy resin (A-1) may be 0.03 mass% or more, 0.1 mass% or more, 0.3 mass% or more, etc., based on 100 mass% of the liquid epoxy resin (A-1). Even when the liquid epoxy resin (A-1) containing chlorine is adopted in this way, a resin composition containing a specific range of the amount of the carbon-containing inorganic filler (B-1) can achieve high insulation. The upper limit of the amount of chlorine contained in the liquid epoxy resin (A-1) is preferably 5 mass% or less, more preferably 3 mass% or less, and even more preferably 1 mass% or less.
[0030] From the above viewpoint, particularly preferred specific examples of the liquid epoxy resin (A-1) include a hexanediol type liquid epoxy resin represented by the following formula (a-1), a trimethylolpropane type liquid epoxy resin represented by the following formula (a-2), a polypropylene glycol type liquid epoxy resin represented by the following formula (a-3), and a neopentyl glycol type liquid epoxy resin represented by the following formula (a-4). In formula (a-3), n represents a number of 0 or more. Commercially available examples of hexanediol type liquid epoxy resins include "ED-503" (viscosity 25 mPa·s, chlorine content 6.5% by mass) and "ED-503G" (viscosity 15 mPa·s, chlorine content 0.3% by mass) manufactured by Adeka Corporation. Commercially available examples of trimethylolpropane type liquid epoxy resins include "ED-505" (viscosity 150 mPa·s, chlorine content 8.0% by mass) manufactured by Adeka Corporation. An example of a commercially available polypropylene glycol type liquid epoxy resin is ADEKA Corporation's "ED-506" (viscosity 60 mPa s, chlorine content 6.0% by mass). An example of a commercially available neopentyl glycol type liquid epoxy resin is ADEKA Corporation's "ED-523T" (viscosity 15 mPa s, chlorine content 5.0% by mass).
[0031] [ka]
[0032] The epoxy equivalent of the liquid epoxy resin (A-1) is preferably in the range of 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 3,000 g / eq., further preferably 80 g / eq. to 2,000 g / eq., and particularly preferably 110 g / eq. to 1,000 g / eq. The epoxy equivalent represents the mass of the resin per equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.
[0033] The resin composition according to one embodiment of the present invention contains a liquid epoxy resin (A-1) in a specific range of amount. The range of the amount of the liquid epoxy resin (A-1) is usually 0.5% by mass or more, preferably 1% by mass or more, more preferably 2% by mass or more, and preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, based on 100% by mass of the non-volatile components in the resin composition. When the amount of the liquid epoxy resin (A-1) is within the above range, it is possible to increase both the fluidity and the insulation reliability, and moreover, it is usually possible to improve the minimum melt viscosity and the heat resistance.
[0034] The amount of the liquid epoxy resin (A-1) is preferably 1% by mass or more, preferably 1.5% by mass or more, more preferably 2% by mass or more, particularly preferably 5% by mass or more, and preferably 40% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less, based on 100% by mass of the resin components in the resin composition. The resin components of the resin composition refer to the non-volatile components of the resin composition, excluding the inorganic filler (B). When the amount of the liquid epoxy resin (A-1) is within the above range, the flowability and insulation reliability can be effectively improved, and usually the minimum melt viscosity and heat resistance can be particularly improved.
[0035] It is preferable that the liquid epoxy resin (A-1) contains a large amount of liquid epoxy resin having a viscosity in the specific range (for example, 1,000 mPa·s or less) at 25°C. The amount of the liquid epoxy resin having a viscosity in the specific range at 25°C is preferably 30 mass% or more, more preferably 40 mass% or more, and even more preferably 50 mass% or more, and usually 100 mass% or less, based on 100 mass% of the total amount of the liquid epoxy resin (A-1). In particular, it is preferable that all of the liquid epoxy resin (A-1) is a liquid epoxy resin having a viscosity of 1,000 mPa·s or less at 25°C. When the amount of the liquid epoxy resin having a viscosity in the specific range at 25°C is within the above range, the fluidity and insulation reliability can be effectively improved, and moreover, usually, the minimum melt viscosity and heat resistance can be particularly improved.
[0036] The (A) epoxy resin may contain (A-2) a solid epoxy resin in combination with (A-1) a liquid epoxy resin. (A-2) solid epoxy resin refers to an epoxy resin that is solid at a temperature of 20° C. As the (A-2) solid epoxy resin, a solid epoxy resin having two or more epoxy groups in one molecule is preferable, and a solid epoxy resin having three or more epoxy groups in one molecule is more preferable.
[0037] Examples of the (A-2) solid epoxy resin include bixylenol type solid epoxy resin, naphthalene type solid epoxy resin, naphthalene type 4-functional solid epoxy resin, naphthol novolac type solid epoxy resin, cresol novolac type solid epoxy resin, dicyclopentadiene type solid epoxy resin, trisphenol type solid epoxy resin, naphthol type solid epoxy resin, biphenyl type solid epoxy resin, naphthylene ether type solid epoxy resin, anthracene type solid epoxy resin, bisphenol A type solid epoxy resin, bisphenol AF type solid epoxy resin, phenol aralkyl type solid epoxy resin, tetraphenylethane type solid epoxy resin, and phenolphthalimidine type solid epoxy resin. The (A-2) solid epoxy resin may be used alone or in combination of two or more.
[0038] From the viewpoint of obtaining a cured product having excellent heat resistance, the (A-2) solid epoxy resin preferably contains a solid epoxy resin containing an aromatic ring, and may contain only a solid epoxy resin containing an aromatic ring. Examples of the solid epoxy resin containing an aromatic ring include bixylenol type solid epoxy resin, naphthalene type solid epoxy resin, naphthalene type 4-functional solid epoxy resin, naphthol novolac type solid epoxy resin, cresol novolac type solid epoxy resin, trisphenol type solid epoxy resin, naphthol type solid epoxy resin, biphenyl type solid epoxy resin, naphthylene ether type solid epoxy resin, anthracene type solid epoxy resin, bisphenol A type solid epoxy resin, bisphenol AF type solid epoxy resin, phenol aralkyl type solid epoxy resin, tetraphenylethane type solid epoxy resin, and phenolphthalimidine type solid epoxy resin.
[0039] Specific examples of the solid epoxy resin (A-2) include "HP4032H" (naphthalene-type solid epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene-type tetrafunctional solid epoxy resin) manufactured by DIC Corporation; "N-690" (cresol novolac-type solid epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac-type solid epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene-type solid epoxy resin) manufactured by DIC Corporation. resins); "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", and "HP6000" (naphthylene ether type solid epoxy resins) manufactured by DIC; "EPPN-502H" (trisphenol type solid epoxy resins) manufactured by Nippon Kayaku; "NC7000L" (naphthol novolac type solid epoxy resins) manufactured by Nippon Kayaku; "NC3000H", "NC3000", "NC3000L", "NC3000FH", and "NC3100" (biphenyl type solid epoxy resins) manufactured by Nippon Kayaku resin); "ESN475V" (naphthol-type solid epoxy resin), "ESN4100V" (naphthalene-type solid epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN485" (naphthol-type solid epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN375" (dihydroxynaphthalene-type solid epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK", "YL7890" (bixylenol-type solid epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "Y L6121" (biphenyl type solid epoxy resin); "YX8800" (anthracene type solid epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YX7700" (phenol aralkyl type solid epoxy resin) manufactured by Mitsubishi Chemical Corporation; "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7760" (bisphenol AF type solid epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YL7800" (fluorene type solid epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1010" (bisphenol A type solid epoxy resin) manufactured by Mitsubishi Chemical Corporation;Examples of such epoxy resins include "jER1031S" (tetraphenylethane-type solid epoxy resin) manufactured by Mitsubishi Chemical Corporation; and "WHR991S" (phenolphthalimidine-type solid epoxy resin) manufactured by Nippon Kayaku Co., Ltd.;
[0040] The weight average molecular weight (Mw) of the solid epoxy resin (A-2) is preferably 100 to 5,000, more preferably 250 to 3,000, and even more preferably 400 to 1,500.
[0041] The epoxy equivalent range of the solid epoxy resin (A-2) may be the same as the epoxy equivalent range of the liquid epoxy resin (A-1).
[0042] When a liquid epoxy resin (A-1) and a solid epoxy resin (A-2) are used in combination as the epoxy resin (A), the mass ratio thereof (liquid epoxy resin (A-1) : solid epoxy resin (A-2)) is preferably 50:1 to 1:50, more preferably 30:1 to 1:30, and particularly preferably 10:1 to 1:10.
[0043] The epoxy resin (A) including the liquid epoxy resin (A-1) and the solid epoxy resin (A-2) preferably contains an epoxy resin having two or more epoxy groups in one molecule. The amount of the epoxy resin (A) having two or more epoxy groups in one molecule is preferably 50% by mass or more, more preferably 60% by mass or more, particularly preferably 70% by mass or more, and is usually 100% by mass or less, based on 100% by mass of the total amount of the epoxy resin (A).
[0044] The amount of the epoxy resin (A) in the resin composition is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less, based on 100% by mass of the non-volatile components in the resin composition. When the amount of the epoxy resin (A) is within the above range, the flowability and insulation reliability can be effectively improved, and usually the minimum melt viscosity and heat resistance can be particularly improved.
[0045] The amount of the epoxy resin (A) in the resin composition is preferably 10% by mass or more, more preferably 30% by mass or more, and even more preferably 50% by mass or more, and is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less, based on 100% by mass of the resin components in the resin composition. When the amount of the epoxy resin (A) is within the above range, the flowability and insulation reliability can be effectively improved, and usually the minimum melt viscosity and heat resistance can be particularly improved.
[0046] [(B) Inorganic filler] The resin composition according to one embodiment of the present invention contains an inorganic filler (B) as component (B). The inorganic filler (B) is usually contained in the resin composition in the form of particles.
[0047] (B) Inorganic filler may be particles of an inorganic compound. (B) Inorganic filler may include, for example, silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica and alumina are preferred, and silica is particularly preferred. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, spherical silica is preferred as silica. The (B) inorganic filler may be used alone or in combination of two or more kinds.
[0048] (B) Inorganic filler contains (B-1) carbon-containing inorganic filler in a specific range of amount. (B-1) carbon-containing inorganic filler means an inorganic filler containing a specific range of amount of carbon. Therefore, (B-1) can be a particle of an inorganic compound containing a specific range of amount of carbon. The carbon content range of (B-1) carbon-containing inorganic filler is usually 0.1 mass% or more, preferably 0.2 mass% or more, more preferably 0.3 mass% or more, particularly preferably 0.4 mass% or more, and preferably 5 mass% or less, more preferably 3 mass% or less, and even more preferably 1 mass% or less. The carbon content of (B-1) carbon-containing inorganic filler does not include the amount of carbon atoms that the surface treatment agent may contain. Therefore, for example, the "carbon content" of (B-1) carbon-containing inorganic filler that has been surface-treated with a surface treatment agent containing carbon atoms does not include the amount of carbon atoms of the surface treatment agent.
[0049] The carbon content of the inorganic filler can be measured by X-ray fluorescence analysis and solid-state NMR. For details on X-ray fluorescence analysis, see, for example, Kyushu University Central Analysis Center "Center News" vol. 40 No. 1, 2021 (published on July 5, 2021). However, as described above, the carbon content of the (B-1) carbon-containing inorganic filler does not include the amount of carbon atoms that the surface treatment agent may contain. Therefore, it is desirable to measure the carbon content of the (B-1) carbon-containing inorganic filler before the surface treatment. For surface-treated inorganic fillers, it is possible to measure the amount of carbon atoms by performing a chemical treatment, such as a strong acid or strong base, to dissolve the surface treatment agent together with the outermost layer of the inorganic filler particles, and then performing a measurement.
[0050] (B-1) carbon-containing inorganic filler is usually a particle containing the above-mentioned inorganic compound as a main component. Therefore, (B-1) carbon-containing inorganic filler may contain the above-mentioned inorganic compound in combination with carbon. Among the above-mentioned inorganic compounds, silica is preferred from the viewpoint of significantly exhibiting the effects of the present invention. Therefore, (B-1) carbon-containing inorganic filler is preferably a silica particle containing a specific range of amount of carbon. The amount of silica contained in the silica particles is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. The amount of silica can be measured by fluorescent X-ray analysis.
[0051] The manufacturing method of the carbon-containing inorganic filler (B-1) described above is not particularly limited. From the viewpoints of energy saving, cost saving, and environmental conservation, it is preferable to manufacture the carbon-containing inorganic filler (B-1) from a plant raw material. For example, plants of the Equisetaceae and Poaceae families may have the property of absorbing and accumulating silicon components from the ground. Therefore, by burning these plants, silica can be manufactured as combustion ash (Patent Publication No. 6389349). Hereinafter, silica manufactured from a plant raw material in this way may be referred to as "biomass silica". Since biomass silica usually contains carbon, it can be used as the carbon-containing inorganic filler (B-1). In addition, the carbon-containing inorganic filler (B-1) may be a commercially available product. An example of a commercially available carbon-containing inorganic filler (B-1) is "Ethical Silica" manufactured by MIT, which is a biomass silica manufactured from rice husks.
[0052] The carbon-containing inorganic filler (B-1) may be used alone or in combination of two or more kinds.
[0053] From the viewpoint of significantly obtaining the desired effects of the present invention, the average particle size of the (B-1) carbon-containing inorganic filler is preferably 0.01 μm or more, more preferably 0.1 μm or more, even more preferably 0.5 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 5 μm or less.
[0054] (B-1) The average particle size of inorganic fillers such as carbon-containing inorganic fillers can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is prepared on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is used as the average particle size. The measurement sample can be prepared by weighing 100 mg of inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing the mixture by ultrasonic waves for 10 minutes. The measurement sample can be measured using a laser diffraction particle size distribution measuring device with blue and red light wavelengths as the light source, and the volume-based particle size distribution of the inorganic filler can be measured using a flow cell method, and the average particle size can be calculated from the obtained particle size distribution as the median diameter. An example of a laser diffraction particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.
[0055] The specific surface area of the (B-1) carbon-containing inorganic filler is preferably 0.1 m from the viewpoint of significantly obtaining the desired effects of the present invention. 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 / g or more, preferably 100m 2 / g or less, more preferably 70m 2 / g or less, more preferably 50m 2 / g or less, particularly preferably 40m 2 The specific surface area of the inorganic filler can be measured by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.
[0056] (B-1) The carbon-containing inorganic filler is preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. Examples of the surface treatment agent include fluorine-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, titanate coupling agents, etc. The surface treatment agent may be used alone or in any combination of two or more.
[0057] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).
[0058] From the viewpoint of improving the dispersibility of the (B-1) carbon-containing inorganic filler, the degree of surface treatment with the surface treatment agent is preferably within a specific range. Specifically, 100 mass% of the (B-1) carbon-containing inorganic filler is preferably surface-treated with 0.2 mass% to 5 mass% of the surface treatment agent, more preferably with 0.2 mass% to 3 mass% of the surface treatment agent, and even more preferably with 0.3 mass% to 2 mass% of the surface treatment agent.
[0059] The resin composition according to one embodiment of the present invention contains (B-1) a carbon-containing inorganic filler in a specific range of amount. The range of the amount of (B-1) carbon-containing inorganic filler is usually 10% by mass or more, preferably 15% by mass or more, more preferably 20% by mass or more, and preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less, based on 100% by mass of non-volatile components in the resin composition. When the amount of (B-1) carbon-containing inorganic filler is within the above range, both the flowability and the insulation reliability can be improved, and furthermore, the minimum melt viscosity and heat resistance can be improved.
[0060] The amount of the carbon-containing inorganic filler (B-1) is preferably 20% by mass or more, more preferably 25% by mass or more, and even more preferably 30% by mass or more, and usually 100% by mass or less, based on 100% by mass of the total amount of the inorganic filler (B). When the amount of the carbon-containing inorganic filler (B-1) is within the above range, the flowability and insulation reliability can be effectively improved, and usually the minimum melt viscosity and heat resistance can be particularly improved.
[0061] The mass ratio of the (B-1) carbon-containing inorganic filler to the (A) epoxy resin ((B-1) carbon-containing inorganic filler / (A) epoxy resin) is preferably in the range of 0.5 or more, more preferably 1 or more, even more preferably 1.2 or more, and particularly preferably 1.5 or more, and is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less. When the mass ratio ((B-1) carbon-containing inorganic filler / (A) epoxy resin) is in the above range, the fluidity and insulation reliability can be effectively improved, and furthermore, usually the minimum melt viscosity and heat resistance can be particularly improved.
[0062] The mass ratio of the (B-1) carbon-containing inorganic filler to the (A-1) liquid epoxy resin ((B-1) carbon-containing inorganic filler / (A-1) liquid epoxy resin) is preferably in the range of 1 or more, more preferably 5 or more, and even more preferably 10 or more, and is preferably 200 or less, more preferably 150 or less, and even more preferably 100 or less. When the mass ratio ((B-1) carbon-containing inorganic filler / (A-1) liquid epoxy resin) is within the above range, the fluidity and insulation reliability can be effectively improved, and furthermore, usually the minimum melt viscosity and heat resistance can be particularly improved.
[0063] The mass ratio of the (B-1) carbon-containing inorganic filler to the "liquid epoxy resin having a viscosity of 1,000 mPa·s or less at 25°C" ((B-1) carbon-containing inorganic filler / "liquid epoxy resin having a viscosity of 1,000 mPa·s or less at 25°C") is preferably in the range of 1 or more, more preferably 5 or more, even more preferably 10 or more, and particularly preferably 20 or more, and is preferably 200 or less, more preferably 150 or less, even more preferably 100 or less, and particularly preferably 70 or less. When the mass ratio ((B-1) carbon-containing inorganic filler / "liquid epoxy resin having a viscosity of 1,000 mPa·s or less at 25°C") is within the above range, the fluidity and insulation reliability can be effectively improved, and furthermore, usually, the minimum melt viscosity and heat resistance can be particularly improved.
[0064] The resin composition according to one embodiment of the present invention may contain (B-2) an arbitrary inorganic filler in combination with (B-1) the carbon-containing inorganic filler. (B-2) The arbitrary inorganic filler refers to an inorganic filler other than (B-1) the carbon-containing inorganic filler, and therefore may refer to an inorganic filler whose carbon content is not within the above-mentioned range.
[0065] (B-2) The optional inorganic filler may be particles of the inorganic compounds described above. Among the inorganic compounds, silica and alumina are preferred, and silica is particularly preferred. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. Moreover, as silica, spherical silica is preferred. (B-2) The optional inorganic filler may be used alone or in combination of two or more kinds.
[0066] (B-2) Examples of commercially available inorganic fillers include "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" manufactured by Tokuyama Corporation; and "MG-005" manufactured by Taiheiyo Cement Corporation.
[0067] From the viewpoint of significantly obtaining the desired effects of the present invention, the average particle size of the optional inorganic filler (B-2) is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and particularly preferably 0.2 μm or more, and is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less.
[0068] The specific surface area of the (B-2) optional inorganic filler is preferably 0.1 m from the viewpoint of significantly obtaining the desired effects of the present invention. 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 / g or more, preferably 100m 2 / g or less, more preferably 70m 2 / g or less, more preferably 50m 2 / g or less, particularly preferably 40m 2 / g or less.
[0069] From the viewpoint of improving moisture resistance and dispersibility, it is preferable that the (B-2) optional inorganic filler is treated with a surface treatment agent. Examples of the surface treatment agent for the (B-2) optional inorganic filler include the same as the examples of the surface treatment agent for the (B-1) carbon-containing inorganic filler. The surface treatment agent may be used alone or in any combination of two or more. The range of the degree of surface treatment by the surface treatment agent for the (B-2) optional inorganic filler may be the same as the range of the degree of surface treatment by the surface treatment agent for the (B-1) carbon-containing inorganic filler.
[0070] The amount of the (B) inorganic filler in the resin composition is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 40% by mass or more, particularly preferably 50% by mass or more, and is preferably 90% by mass or less, more preferably 85% by mass or less, particularly preferably 80% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the (B) inorganic filler is within the above range, the flowability and insulation reliability can be effectively improved, and usually the minimum melt viscosity and heat resistance can be particularly improved.
[0071] [(C) Hardener] The resin composition according to one embodiment of the present invention may further contain a (C) curing agent as an optional component in combination with the (A) and (B) components. The (C) curing agent as the (C) component does not include those corresponding to the above-mentioned (A) and (B) components, unless otherwise specified. The (C) curing agent may have a function of reacting with the (A) epoxy resin to cure the resin composition. The (C) curing agent may be used alone or in combination of two or more types.
[0072] Preferred examples of the (C) curing agent include active ester-based curing agents, cyanate ester-based curing agents, phenol-based curing agents, carbodiimide-based curing agents, acid anhydride-based curing agents, amine-based curing agents, benzoxazine-based curing agents, and thiol-based curing agents.
[0073] As the active ester curing agent, generally, a compound having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, is preferably used. The active ester curing agent is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester curing agent obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester curing agent obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.
[0074] Specifically, the active ester curing agent is preferably a dicyclopentadiene type active ester curing agent, a naphthalene type active ester curing agent containing a naphthalene structure, an active ester curing agent containing an acetylated product of phenol novolac, or an active ester curing agent containing a benzoylated product of phenol novolac, and among these, at least one selected from a dicyclopentadiene type active ester curing agent and a naphthalene type active ester curing agent is more preferable. As the dicyclopentadiene type active ester curing agent, an active ester curing agent containing a dicyclopentadiene type diphenol structure is preferable.
[0075] Commercially available active ester curing agents include, for example, "EXB9451", "EXB9460", "EXB9460S", "EXB-8000L", "EXB-8000L-65M", "EXB-8000L-65TM", "HPC-8000L-65TM", "HPC-8000", "HPC-8000-65T", "HPC-8000H", and "HPC-8000H-65TM" (manufactured by DIC Corporation) as active ester curing agents containing a dicyclopentadiene-type diphenol structure; and "HP-B-8151-62T", "EXB-8100L-65T", "EXB-8150-60T", "EXB-8150-62T", " Examples of such hardeners include "EXB-9416-70BK", "HPC-8150-60T", "HPC-8150-62T", "EXB9416-70BK", and "EXB-8" (manufactured by DIC Corporation); "EXB9401" (manufactured by DIC Corporation) as a phosphorus-containing active ester hardener; "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester hardener which is an acetylated product of phenol novolac; "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation) as active ester hardeners which are benzoylated products of phenol novolac; and "PC1300-02-65MA" (manufactured by Air Water Corporation) as an active ester hardener containing a styryl group and a naphthalene structure.
[0076] As the cyanate ester-based curing agent, a compound having one or more, preferably two or more, cyanate groups in one molecule can be used. Examples of the cyanate ester-based curing agent include bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate)phenylpropane, ... Examples of the cyanate ester curing agent include bifunctional cyanate ester curing agents such as bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanatephenyl-1-(methylethylidene))benzene, bis(4-cyanatephenyl)thioether, and bis(4-cyanatephenyl)ether; polyfunctional cyanate ester curing agents derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate ester curing agents are partially triazine-converted. Specific examples of the cyanate ester curing agent include "PT30" and "PT60" (both phenol novolac-type polyfunctional cyanate ester curing agents), "BA230", and "BA230S75" (prepolymers in which bisphenol A dicyanate is partially or entirely triazine-converted to form a trimer), all of which are manufactured by Lonza Japan Co., Ltd.
[0077] As the phenol-based curing agent, a compound having one or more, preferably two or more, hydroxyl groups bonded to an aromatic ring such as a benzene ring or a naphthalene ring in one molecule can be used. From the viewpoint of heat resistance and water resistance, a phenol-based curing agent having a novolac structure is preferred. From the viewpoint of adhesion, a nitrogen-containing phenol-based curing agent is preferred, and a triazine skeleton-containing phenol-based curing agent is more preferred. Among them, from the viewpoint of highly satisfying heat resistance, water resistance, and adhesion, a triazine skeleton-containing phenol novolac-based curing agent is preferred. Specific examples of phenol-based curing agents include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-375", and "SN-395" manufactured by Nippon Steel Chemical & Material Co., Ltd.; and "LA-7052", "LA-7054", "LA-3018", "LA-3018-50P", "LA-1356", "TD2090", and "TD-2090-60M" manufactured by DIC Corporation.
[0078] As the carbodiimide-based curing agent, a compound having one or more, preferably two or more, carbodiimide groups in one molecule can be used. Specific examples of the carbodiimide-based curing agent include aliphatic biscarbodiimides such as tetramethylene-bis(t-butylcarbodiimide) and cyclohexane bis(methylene-t-butylcarbodiimide); aromatic biscarbodiimides such as phenylene-bis(xylylcarbodiimide); aliphatic polycarbodiimides such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), and poly(isophoronecarbodiimide); poly(phenylenecarbodiimide), poly( Examples of polycarbodiimides include aromatic polycarbodiimides such as poly(naphthylenecarbodiimide), poly(tolylenecarbodiimide), poly(methyldiisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), poly(diethylphenylenecarbodiimide), poly(triisopropylphenylenecarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(xylylenecarbodiimide), poly(tetramethylxylylenecarbodiimide), poly(methylenediphenylenecarbodiimide), and poly[methylenebis(methylphenylene)carbodiimide]. Commercially available carbodiimide curing agents include, for example, "Carbodilite V-02B", "Carbodilite V-03", "Carbodilite V-04K", "Carbodilite V-07", and "Carbodilite V-09" manufactured by Nisshinbo Chemical Inc.; and "Stavaxol P", "Stavaxol P400", and "Hi-Kasil 510" manufactured by Rhein Chemie.
[0079] As the acid anhydride curing agent, a compound having one or more, preferably two or more, acid anhydride groups in one molecule can be used. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenonetetracarboxylic dianhydride, and the like. Examples of acid anhydrides include anhydrides, biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resin, which is a copolymer of styrene and maleic acid. Commercially available acid anhydride curing agents include, for example, "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by New Japan Chemical Co., Ltd.; "YH-306" and "YH-307" manufactured by Mitsubishi Chemical Corporation; "HN-2200" and "HN-5500" manufactured by Hitachi Chemical Co., Ltd.; and "EF-30", "EF-40", "EF-60", and "EF-80" manufactured by Clay Valley.
[0080] As the amine-based curing agent, a compound having one or more, preferably two or more, amino groups in one molecule can be used. As the amine-based curing agent, for example, aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc. can be mentioned, among which aromatic amines are preferred. As the amine-based curing agent, primary amines or secondary amines are preferred, and primary amines are more preferred. Specific examples of the amine-based curing agent include 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxyphenyl)propane, and the like. propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, and the like. Commercially available amine-based curing agents include, for example, "SEIKACURE-S" manufactured by Seika Corporation; "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd.; "Epicure W" manufactured by Mitsubishi Chemical Corporation; and "DTDA" manufactured by Sumitomo Seika Chemicals Co., Ltd.
[0081] Specific examples of benzoxazine-based curing agents include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Corporation; "HFB2006M" manufactured by Showa Polymer Co., Ltd.; and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.
[0082] Examples of thiol-based curing agents include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.
[0083] The active group equivalent of the (C) curing agent is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 350 g / eq. The active group equivalent represents the mass of the resin per equivalent of the active group.
[0084] When the number of epoxy groups in the (A) epoxy resin is taken as 1, the number of active groups in the (C) curing agent is preferably 0.01 or more, more preferably 0.1 or more, even more preferably 0.2 or more, and preferably 10 or less, more preferably 5 or less, even more preferably 1 or less. The "number of epoxy groups in the (A) epoxy resin" refers to the total value obtained by dividing the mass of the non-volatile components of the (A) epoxy resin present in the resin composition by the epoxy equivalent. The "number of active groups in the (C) curing agent" refers to the total value obtained by dividing the mass of the non-volatile components of the (C) curing agent present in the resin composition by the active group equivalent.
[0085] The amount of the (C) curing agent in the resin composition may be 0% by mass or may be greater than 0% by mass, and is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 5% by mass or more, and is preferably 40% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less, relative to 100% by mass of the non-volatile components of the resin composition.
[0086] The amount of the (C) curing agent in the resin composition may be 0% by mass or may be greater than 0% by mass, and is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 20% by mass or more, and is preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less, relative to 100% by mass of the resin component of the resin composition.
[0087] [(D) Curing accelerator] The resin composition according to one embodiment of the present invention may further contain a curing accelerator (D) as an optional component. The curing accelerator (D) as the component (D) does not include those corresponding to the above-mentioned components (A) to (C) unless otherwise specified. The curing accelerator (D) functions as a curing catalyst that accelerates the curing of the epoxy resin (A).
[0088] Examples of the (D) curing accelerator include phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, imidazole-based curing accelerators, metal-based curing accelerators, and amine-based curing accelerators. Among these, imidazole-based curing accelerators are preferred. The (D) curing accelerators may be used alone or in combination of two or more.
[0089] Examples of the phosphorus-based curing accelerator include aliphatic phosphonium salts such as tetrabutyl phosphonium bromide, tetrabutyl phosphonium chloride, tetrabutyl phosphonium acetate, tetrabutyl phosphonium decanoate, tetrabutyl phosphonium laurate, bis(tetrabutyl phosphonium)pyromellitate, tetrabutyl phosphonium hydrogenhexahydrophthalate, tetrabutyl phosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butyldimethylphosphonium tetraphenylborate; methyl triphenyl phosphonium bromide, ethyl triphenyl phosphonium bromide, propyl triphenyl phosphonium bromide, butyl triphenyl phosphonium bromide, benzyl triphenyl phosphonium chloride, tetraphenyl phosphonium bromide, p-tolyl triphenyl phosphonium tetra-p-tolylborate, tetraphenyl phosphonium bromide, and the like. aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples of aromatic phosphines include tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether.
[0090] Examples of the urea-based curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. aromatic dimethylureas such as butylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluene bisdimethylurea].
[0091] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide.
[0092] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-methylimidazole. Phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct , 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and other imidazole compounds and adducts of imidazole compounds and epoxy resins. Commercially available imidazole curing accelerators include, for example, "1B2PZ", "2E4MZ", "2MZA-PW", "2MZ-OK", "2MA-OK", "2MA-OK-PW", "2PHZ", "2PHZ-PW", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", and "C11Z-A" manufactured by Shikoku Chemical Industry Co., Ltd.; and "P200-H50" manufactured by Mitsubishi Chemical Corporation.
[0093] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.
[0094] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4,0)-undecene, etc. Commercially available amine-based curing accelerators may be used, such as "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.
[0095] The amount of the (D) curing accelerator in the resin composition may be 0% by mass or may be more than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, even more preferably 0.03% by mass or more, and is preferably 2% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less, relative to 100% by mass of the non-volatile components of the resin composition.
[0096] The amount of the (D) curing accelerator in the resin composition may be 0% by mass or may be greater than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, and is preferably 5% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less, relative to 100% by mass of the resin component of the resin composition.
[0097] [(E) Thermoplastic resin] The resin composition according to one embodiment of the present invention may further contain a thermoplastic resin (E) as an optional component. The thermoplastic resin (E) as the component (E) does not include those corresponding to the above-mentioned components (A) to (D) unless otherwise specified.
[0098] Examples of the (E) thermoplastic resin include phenoxy resin, polyimide resin, polyvinyl acetal resin, polyolefin resin, polybutadiene resin, polyamideimide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polycarbonate resin, polyetheretherketone resin, polyester resin, etc. The (E) thermoplastic resin may be used alone or in combination of two or more kinds.
[0099] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group. Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton); "FX280" and "FX293" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", "YL7482", and "YL7891BH30" manufactured by Mitsubishi Chemical Corporation.
[0100] Specific examples of polyimide resins include "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., and "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd.
[0101] Examples of polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred.Specific examples of polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd.; S-LEC BH series, BX series (e.g. BX-5Z), KS series (e.g. KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.
[0102] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymer.
[0103] Examples of polybutadiene resins include hydrogenated polybutadiene skeleton-containing resins, hydroxy group-containing polybutadiene resins, phenolic hydroxy group-containing polybutadiene resins, carboxy group-containing polybutadiene resins, acid anhydride group-containing polybutadiene resins, epoxy group-containing polybutadiene resins, isocyanate group-containing polybutadiene resins, urethane group-containing polybutadiene resins, polyphenylene ether-polybutadiene resins, and the like.
[0104] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.
[0105] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.
[0106] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.
[0107] A specific example of the polyphenylene ether resin is NORYL SA90 manufactured by SABIC, etc. A specific example of the polyetherimide resin is ULTEM manufactured by GE, etc.
[0108] Examples of polycarbonate resins include hydroxyl group-containing carbonate resins, phenolic hydroxyl group-containing carbonate resins, carboxyl group-containing carbonate resins, acid anhydride group-containing carbonate resins, isocyanate group-containing carbonate resins, and urethane group-containing carbonate resins. Specific examples of polycarbonate resins include "FPC0220" manufactured by Mitsubishi Gas Chemical Co., Ltd., "T6002" and "T6001" (polycarbonate diol) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090", and "C-3090" (polycarbonate diol) manufactured by Kuraray Co., Ltd. Specific examples of polyether ether ketone resins include "Sumiploy K" manufactured by Sumitomo Chemical Co., Ltd.
[0109] Examples of polyester resins include polyethylene terephthalate resins, polyethylene naphthalate resins, polybutylene terephthalate resins, polybutylene naphthalate resins, polytrimethylene terephthalate resins, polytrimethylene naphthalate resins, and polycyclohexane dimethyl terephthalate resins.
[0110] The weight average molecular weight (Mw) of the thermoplastic resin (E) is preferably greater than 5,000, more preferably at least 8,000, even more preferably at least 10,000, particularly preferably at least 20,000, and is preferably at most 100,000, more preferably at most 70,000, even more preferably at most 60,000, particularly preferably at most 50,000. The weight average molecular weight can be measured as a polystyrene-equivalent value by gel permeation chromatography (GPC).
[0111] The amount of the (E) thermoplastic resin in the resin composition may be 0% by mass or may be greater than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, and is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, relative to 100% by mass of the non-volatile components of the resin composition.
[0112] The amount of the (E) thermoplastic resin in the resin composition may be 0% by mass or may be greater than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 1% by mass or more, and is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, relative to 100% by mass of the resin components of the resin composition.
[0113] [(F) Radical polymerizable compound] The resin composition according to one embodiment of the present invention may further contain a radical polymerizable compound (F) as an optional component. The radical polymerizable compound (F) as the component (F) does not include those corresponding to the above-mentioned components (A) to (E) unless otherwise specified. The radical polymerizable compound (F) may be used alone or in combination of two or more kinds.
[0114] The radical polymerizable compound (F) may contain an ethylenically unsaturated bond. Thus, the radical polymerizable compound (F) may have a radical polymerizable group containing an ethylenically unsaturated bond. Examples of the radical polymerizable group include unsaturated hydrocarbon groups such as vinyl, allyl, 1-propenyl, 3-cyclohexenyl, 3-cyclopentenyl, 2-vinylphenyl, 3-vinylphenyl, and 4-vinylphenyl; and α,β-unsaturated carbonyl groups such as acryloyl, methacryloyl, and maleimide groups (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl groups). The radical polymerizable compound (F) preferably has two or more radical polymerizable groups.
[0115] Examples of the (F) radically polymerizable compound include (meth)acrylic radically polymerizable compounds, styrene radically polymerizable compounds, allyl radically polymerizable compounds, and maleimide radically polymerizable compounds.
[0116] The (meth)acrylic radical polymerizable compound is, for example, a compound having one or more, preferably two or more, acryloyl groups and / or methacryloyl groups. Examples of the (meth)acrylic radical polymerizable compound include cyclohexane-1,4-dimethanol di(meth)acrylate, cyclohexane-1,3-dimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,2-diphenylmethane di(meth)acrylate, 1,3-diphenylmethane di(meth)acrylate, 1,4-diphenylmethane di(meth)acrylate, 1,5-diphenylmethane di(meth)acrylate, 1,6-diphenylmethane di(meth)acrylate, 1,8-diphenylmethane di(meth)acrylate, 1,9-diphenylmethane ...5-diphenylmethane di(meth)acrylate, 1,5-diphenylmethane di(meth)acrylate, 1,6-diphenylmethane di(meth)acrylate, 1,8-diphenylmethane di(meth)acrylate, 1,9-diphenylmethane di(meth)acrylate, 1,5-diphenylmethane di(meth)acrylate, 1,5-diphenylmethane di(meth)acrylate, 1,5-diphenylmethane di(meth)acrylate, 1,5-diphenylmethane aliphatic (meth)acrylic acid ester compounds with low molecular weight (molecular weight less than 1000), such as dioxane glycol di(meth)acrylate, 3,6-dioxa-1,8-octanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, glycerin tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; Examples of the ether-containing (meth)acrylic acid ester compound include low molecular weight (molecular weight less than 1000) ether-containing (meth)acrylic acid ester compounds such as 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, ethoxylated bisphenol A di(meth)acrylate, and propoxylated bisphenol A di(meth)acrylate; low molecular weight (molecular weight less than 1000) isocyanurate-containing (meth)acrylic acid ester compounds such as tris(3-hydroxypropyl)isocyanurate tri(meth)acrylate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, and ethoxylated isocyanuric acid tri(meth)acrylate; and high molecular weight (molecular weight 1000 or more) acrylic acid ester compounds such as (meth)acrylic modified polyphenylene ether resin.Examples of commercially available (meth)acrylic radically polymerizable compounds include "A-DOG" (dioxane glycol diacrylate) manufactured by Shin-Nakamura Chemical Co., Ltd., "DCP-A" (tricyclodecane dimethanol diacrylate) and "DCP" (tricyclodecane dimethanol dimethacrylate) manufactured by Kyoeisha Chemical Co., Ltd., "KAYARAD R-684" (tricyclodecane dimethanol diacrylate) and "KAYARAD R-604" (dioxane glycol diacrylate) manufactured by Nippon Kayaku Co., Ltd., and "SA9000" and "SA9000-111" (methacrylic-modified polyphenylene ether) manufactured by SABIC Innovative Plastics.
[0117] The styrene radical polymerizable compound is, for example, a compound having one or more, preferably two or more, vinyl groups directly bonded to an aromatic carbon atom. Examples of the styrene radical polymerizable compound include low molecular weight (molecular weight less than 1000) styrene compounds such as divinylbenzene, 2,4-divinyltoluene, 2,6-divinylnaphthalene, 1,4-divinylnaphthalene, 4,4'-divinylbiphenyl, 1,2-bis(4-vinylphenyl)ethane, 2,2-bis(4-vinylphenyl)propane, and bis(4-vinylphenyl)ether; high molecular weight (molecular weight 1000 or more) styrene compounds such as vinylbenzyl-modified polyphenylene ether resin and styrene-divinylbenzene copolymer. Examples of commercially available styrene-based radically polymerizable compounds include "ODV-XET(X03)", "ODV-XET(X04)", and "ODV-XET(X05)" (styrene-divinylbenzene copolymers) manufactured by Nippon Steel Chemical & Material Co., Ltd., and "OPE-2St 1200" and "OPE-2St 2200" (vinylbenzyl-modified polyphenylene ether resins) manufactured by Mitsubishi Gas Chemical Co., Inc.
[0118] The allyl radical polymerizable compound is, for example, a compound having one or more, preferably two or more, allyl groups. Examples of allyl radical polymerizable compounds include aromatic carboxylic acid allyl ester compounds such as diallyl diphenate, triallyl trimellitate, diallyl phthalate, diallyl isophthalate, diallyl terephthalate, diallyl 2,6-naphthalenedicarboxylate, and diallyl 2,3-naphthalenecarboxylate; isocyanuric acid allyl ester compounds such as 1,3,5-triallyl isocyanurate and 1,3-diallyl-5-glycidyl isocyanurate; epoxy-containing aromatic allyl compounds such as 2,2-bis[3-allyl-4-(glycidyloxy)phenyl]propane; benzoxazine-containing aromatic allyl compounds such as bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane; ether-containing aromatic allyl compounds such as 1,3,5-triallyl ether benzene; and allyl silane compounds such as diallyl diphenyl silane. Commercially available allyl radical polymerizable compounds include, for example, "TAIC" (1,3,5-triallyl isocyanurate) manufactured by Nippon Kasei Chemical Industry Co., Ltd., "DAD" (diallyl diphenate) manufactured by Nisshoku Techno Fine Chemical Co., Ltd., "TRIAM-705" (triallyl trimellitate) manufactured by Wako Pure Chemical Industries, Ltd., trade name "DAND" (2,3-naphthalene carboxylate diallyl) manufactured by Nippon Distillation Industry Co., Ltd., "ALP-d" (bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane) manufactured by Shikoku Kasei Corporation, "RE-810NM" (2,2-bis[3-allyl-4-(glycidyloxy)phenyl]propane) manufactured by Nippon Kayaku Co., Ltd., and "DA-MGIC" (1,3-diallyl-5-glycidyl isocyanurate) manufactured by Shikoku Kasei Corporation.
[0119] The maleimide radical polymerizable compound is, for example, a compound having one or more, preferably two or more, maleimide groups. The maleimide radical polymerizable compound may be an aliphatic maleimide compound containing an aliphatic amine skeleton, or an aromatic maleimide compound containing an aromatic amine skeleton. Commercially available maleimide radical polymerizable compounds include, for example, "SLK-2600" manufactured by Shin-Etsu Chemical Co., Ltd., "BMI-1500", "BMI-1700", "BMI-3000J", "BMI-689", and "BMI-2500" (dimer diamine structure-containing maleimide compounds) manufactured by DigiCner Molecules, Inc., "BMI-6100" (aromatic maleimide compound) manufactured by DigiCner Molecules, "MIR-5000-60T" and "MIR-3000-70MT" (biphenylaralkyl-type maleimide compounds) manufactured by Nippon Kayaku Co., Ltd., "BMI-70" and "BMI-80" manufactured by K.I. Chemical Industry Co., Ltd., and "BMI-2300" and "BMI-TMH" manufactured by Daiwa Kasei Kogyo Co., Ltd. In addition, as the maleimide-based radically polymerizable compound, a maleimide resin (maleimide compound containing an indane ring skeleton) disclosed in the Japan Institute of Invention and Innovation's Technical Journal Publication No. 2020-500211 may be used.
[0120] The ethylenically unsaturated bond equivalent of the radical polymerizable compound (F) is preferably 20 g / eq. to 3,000 g / eq., more preferably 50 g / eq. to 2,500 g / eq., further preferably 70 g / eq. to 2,000 g / eq., and particularly preferably 90 g / eq. to 1,500 g / eq. The ethylenically unsaturated bond equivalent represents the mass of the radical polymerizable compound per equivalent of the ethylenically unsaturated bond.
[0121] The weight average molecular weight (Mw) of the radical polymerizable compound (F) is preferably 40,000 or less, more preferably 10,000 or less, further preferably 5,000 or less, and particularly preferably 3,000 or less. The lower limit is not particularly limited, but may be, for example, 150 or more. The weight average molecular weight can be measured as a polystyrene-equivalent value by gel permeation chromatography (GPC).
[0122] The amount of the (F) radically polymerizable compound in the resin composition may be 0% by mass or may be more than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.5% by mass or more, and is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less, relative to 100% by mass of non-volatile components in the resin composition.
[0123] The amount of the (F) radically polymerizable compound in the resin composition may be 0% by mass or may be more than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 1% by mass or more, and is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, relative to 100% by mass of the resin components in the resin composition.
[0124] [(G) Optional Additives] The resin composition according to one embodiment of the present invention may further contain (G) an optional additive as an optional component. Examples of the optional additive (G) include organic fillers such as rubber particles; organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, and diazo yellow; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as bentone and montmorillonite; defoamers such as silicone-based defoamers, acrylic-based defoamers, fluorine-based defoamers, and vinyl resin-based defoamers; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers; adhesion improvers such as urea silane; triazole-based adhesion imparting agents, tetrazole-based adhesion imparting agents, triazine-based adhesion imparting agents, and the like. Examples of the additives include adhesion-imparting agents such as adhesion-imparting agents; antioxidants such as hindered phenol-based antioxidants; fluorescent whitening agents such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; flame retardants such as phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, red phosphorus), nitrogen-based flame retardants (e.g., melamine sulfate), and halogen-based flame retardants; dispersants such as phosphate ester-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers. (G) Optional additives may be used alone or in combination of two or more.
[0125] [(H) Solvent] The resin composition according to one embodiment of the present invention may further contain a (H) solvent as an optional volatile component in combination with the non-volatile components such as the above-mentioned (A) to (G) components. As the (H) solvent, an organic solvent is usually used. Examples of the organic solvent include ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; ether-based solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, and anisole; alcohol-based solvents such as methanol, ethanol, propanol, butanol, and ethylene glycol; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, and methyl methoxypropionate. Examples of suitable solvents include ether ester solvents such as ethyl acetate, ester alcohol solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate, ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butylcarbitol), amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone, sulfoxide solvents such as dimethyl sulfoxide, nitrile solvents such as acetonitrile and propionitrile, aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane, and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. The (H) solvent may be used alone or in combination of two or more.
[0126] The amount of (H) solvent is not particularly limited, but may be, for example, 60 mass% or less, 40 mass% or less, 30 mass% or less, 20 mass% or less, 15 mass% or less, 10 mass% or less, etc., relative to 100 mass% of all components of the resin composition, or may be 0 mass%.
[0127] [Method of producing resin composition] The resin composition according to one embodiment of the present invention can be produced, for example, by mixing the above-mentioned components. The above-mentioned components may be mixed in part or in whole simultaneously, or may be mixed in order. In the process of mixing each component, the temperature may be appropriately set, and thus heating and / or cooling may be performed temporarily or throughout. In addition, stirring or shaking may be performed in the process of mixing each component.
[0128] [Characteristics of resin composition] The resin composition according to one embodiment of the present invention can have high fluidity. The fluidity of the resin composition can be evaluated by undulation. The undulation represents the difference between the maximum and minimum heights of the surface of a layer formed from the resin composition. In general, the smaller the undulation, the higher the fluidity of the resin composition.
[0129] In one example, a conductor layer is formed in a comb-like pattern on a certain plane. The "pattern" of the conductor layer refers to the shape of the conductor layer as viewed from the thickness direction. In this case, the conductor layer is formed to a thickness of 35 μm and L / S=160 μm / 160 μm. L / S refers to the ratio (line / space) of the line L (wiring width) and space S (spacing width) of the conductor layer. A layer is formed by a resin composition on the plane on which the conductor layer is formed. Then, the resin composition layer is thermally cured to form an insulating layer. The height of the surface of this insulating layer (the surface opposite to the conductor layer) is measured, and the difference between the highest height and the lowest height is measured as the undulation. Usually, the surface of the insulating layer is highest in the part on the conductor layer, and the surface of the insulating layer is lowest in the part other than the part on the conductor layer. When the undulation is measured as in this example, the undulation of the resin composition according to one embodiment of the present invention is preferably 3.0 μm or less, more preferably 2.0 μm or less. As a specific method for measuring undulations, the method described in <Test Example 3: Measurement of undulations> in the Examples section described later can be adopted.
[0130] The resin composition according to one embodiment of the present invention can usually have a low minimum melt viscosity. For example, when the minimum melt viscosity is measured by the method described in <Test Example 2: Measurement of minimum melt viscosity of resin composition> in the Examples below, the minimum melt viscosity of the resin composition according to one embodiment of the present invention is preferably less than 4,000 poise, more preferably 3,500 poise or less, and even more preferably 2,900 poise or less. From the viewpoint of smoothly forming a thick insulating layer, the lower limit may be, for example, 500 poise or more, 700 poise or more, etc.
[0131] A cured product is obtained by curing the resin composition according to one embodiment of the present invention. During the curing, heat is usually applied to the resin composition. Thus, among the components contained in the resin composition, volatile components such as (H) solvent can be volatilized by heat during curing, but non-volatile components such as components (A) to (G) do not volatilize by heat during curing. Thus, the cured product of the resin composition can contain the non-volatile components of the resin composition or their reaction products.
[0132] According to the resin composition of one embodiment of the present invention, a cured product with high insulation reliability can be obtained. The insulation reliability of the cured product can be evaluated by the insulation resistance value of the cured product after a durability test in which a voltage is applied in a high-temperature, high-humidity environment is performed. In one example, the resin composition of one embodiment of the present invention is thermally cured under conditions of 190°C for 90 minutes to obtain a cured product, and a durability test is performed in which a voltage of 3.3 V is applied to the cured product in an environment of 130°C and 85% RH for 100 hours. When the durability test is performed in this manner, the insulation resistance value of the cured product measured using a comb-tooth electrode with a line / space of 15 μm / 15 μm is preferably 1.0×10 8 Ω or more, preferably 1.0×10 9 The upper limit is preferably as large as possible, for example, 1.0×10 14 As a specific method for evaluating the insulation reliability, the method described in <Test Example 4: Evaluation of insulation reliability> in the Examples described later can be adopted.
[0133] According to the resin composition according to one embodiment of the present invention, a cured product having excellent heat resistance can usually be obtained. The heat resistance of the cured product can be expressed, for example, by the glass transition temperature. In one example, the glass transition temperature of the cured product obtained by thermally curing the resin composition according to one embodiment of the present invention under the curing conditions of 190°C and 90 minutes can be preferably 130°C or higher, more preferably 140°C or higher, and even more preferably 150°C or higher. The upper limit of the glass transition temperature is preferably higher, and can be, for example, 200°C or lower, 190°C or lower, or 180°C or lower. The glass transition temperature can be measured by performing thermomechanical analysis by a tensile load method under the measurement conditions of a load of 1 g and a temperature rise rate of 5°C / min. A specific method for measuring the glass transition temperature can be adopted, as described in <Test Example 1: Measurement of glass transition temperature and linear thermal expansion coefficient of cured product> in the examples described later.
[0134] According to the resin composition of one embodiment of the present invention, a cured product having excellent reflow resistance can be obtained. The reflow resistance can be evaluated by forming a conductor layer on an insulating layer formed by curing the resin composition, and performing a reflow resistance test including heating. In one example, a conductor layer is formed by plating on an insulating layer formed by thermally curing the resin composition of one embodiment of the present invention by heating at 130°C for 30 minutes and at 170°C for 30 minutes, and two samples of 100 mm x 50 mm are obtained. Then, a reflow resistance test is performed in which the samples are passed 10 times through a reflow device that reproduces a solder reflow temperature of a peak temperature of 260°C (the reflow temperature profile is in accordance with IPC / JEDEC J-STD-020C). In this case, the number of abnormalities such as blisters is preferably 4 or less, and more preferably 0. A specific method for evaluating the reflow resistance can be adopted as described in <Test Example 5: Evaluation of Reflow Resistance> in the Examples described later.
[0135] According to the resin composition of one embodiment of the present invention, a cured product having a small linear thermal expansion coefficient can be obtained. In one example, the average linear thermal expansion coefficient in the range of 25°C to 150°C of the cured product obtained by thermally curing the resin composition of one embodiment of the present invention under the curing conditions of 190°C and 90 minutes is preferably 30 ppm or less, more preferably 25 ppm or less, and even more preferably 23 ppm or less. The linear thermal expansion coefficient can be measured by performing thermomechanical analysis by a tensile load method under the measurement conditions of a load of 1 g and a temperature rise rate of 5°C / min. A specific method for measuring the linear thermal expansion coefficient can be adopted as described in <Test Example 1: Measurement of glass transition temperature and linear thermal expansion coefficient of cured product> in the examples described later.
[0136] The cured product of the resin composition according to one embodiment of the present invention can usually have excellent dielectric properties. For example, the relative dielectric constant of the cured product is preferably 5.0 or less, more preferably 4.0 or less, and even more preferably 3.5 or less. The lower limit of the relative dielectric constant is not particularly limited, and can be, for example, 1.5 or more, 2.0 or more, etc. Also, for example, the dielectric tangent of the cured product is preferably 0.0200 or less, more preferably 0.0100 or less, even more preferably 0.0050 or less, and particularly preferably 0.0030 or less. The lower limit of the dielectric tangent is not particularly limited, and can be, for example, 0.0005 or more. The relative dielectric constant and dielectric tangent of the cured product can be measured by a cavity resonance perturbation method under conditions of a measurement frequency of 5.8 GHz and a measurement temperature of 23 ° C. using a cured product obtained by thermally curing the resin composition under a curing condition of 190 ° C. and 90 minutes. As a measuring device, for example, Agilent Technologies' "HP8362B" can be used.
[0137] [Uses of resin composition] The resin composition according to one embodiment of the present invention can be used as a resin composition for insulating purposes, and can be particularly preferably used as a resin composition for forming an insulating layer (resin composition for forming an insulating layer). For example, the resin composition according to this embodiment can be preferably used as a resin composition for forming an insulating layer of a semiconductor chip package (resin composition for insulating layer of a semiconductor chip package) and a resin composition for forming an insulating layer of a circuit board (including a printed wiring board) (resin composition for insulating layer of a circuit board). In particular, the resin composition is suitable for forming an interlayer insulating layer provided between conductor layers.
[0138] Examples of semiconductor chip packages include FC-CSP, MIS-BGA package, ETS-BGA package, Fan-out type WLP (Wafer Level Package), Fan-in type WLP, Fan-out type PLP (Panel Level Package), and Fan-in type PLP.
[0139] The resin composition may also be used as an underfill material, for example, as a material for MUF (Molding Under Filling) that is used after a semiconductor chip is connected to a substrate.
[0140] Furthermore, the resin composition can be used in a wide range of applications in which resin compositions are used, such as sheet-like laminate materials such as resin sheets and prepregs, solder resists, die bonding materials, semiconductor encapsulating materials, hole filling resins, and component embedding resins.
[0141] [Sheet-type laminated material] The resin composition may be used by coating in the form of a varnish, but from an industrial perspective, it is preferable to use the resin composition in the form of a sheet-like laminate material containing the resin composition.
[0142] As the sheet-like laminate material, the following resin sheets and prepregs are preferred.
[0143] In one embodiment, the resin sheet includes a support and a resin composition layer formed on the support. The resin composition layer is formed of the above-mentioned resin composition. Thus, the resin composition layer usually contains a resin composition, and preferably contains only the resin composition.
[0144] The thickness of the resin composition layer is preferably 50 μm or less, more preferably 40 μm or less, from the viewpoint of thinning and of being able to provide a cured product having excellent insulation even if it is thin, by using the resin composition. The lower limit of the thickness of the resin composition layer is not particularly limited, but may be 5 μm or more, 10 μm or more, etc.
[0145] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.
[0146] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0147] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.
[0148] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, or an antistatic treatment.
[0149] As the support, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.
[0150] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.
[0151] In one embodiment, the resin sheet may further include an optional layer as necessary. For example, such an optional layer may be a protective film equivalent to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, it is possible to suppress adhesion of dirt and scratches on the surface of the resin composition layer.
[0152] The resin sheet can be produced, for example, by preparing a liquid (varnish-like) resin composition as is or by dissolving the resin composition in a solvent, applying this onto a support using a coating device such as a die coater, and then drying to form a resin composition layer.
[0153] The solvent may be the same as the (H) solvent described as a component of the resin composition. One type of solvent may be used alone, or two or more types may be used in combination.
[0154] Drying may be performed by a drying method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of the solvent in the resin composition layer is usually 10 mass % or less, preferably 5 mass % or less. Although it varies depending on the boiling point of the solvent in the resin composition, for example, when a resin composition containing 30 mass % to 60 mass % of the solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.
[0155] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it is usually possible to use the resin sheet by peeling off the protective film.
[0156] In one embodiment, the prepreg is formed by impregnating a sheet-like fiber substrate with the above-mentioned resin composition.
[0157] The sheet-like fiber substrate used for the prepreg may be, for example, a commonly used substrate for prepreg, such as glass cloth, aramid nonwoven fabric, or liquid crystal polymer nonwoven fabric. From the viewpoint of thinning, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited, and is usually 10 μm or more.
[0158] The prepreg can be produced by a method such as a hot melt method or a solvent method.
[0159] The thickness of the prepreg can be in the same range as that of the resin composition layer in the resin sheet described above.
[0160] The sheet-like laminate material can be suitably used, for example, to form an insulating layer in the manufacture of a semiconductor chip package (resin sheet for insulating a semiconductor chip package). Examples of applicable semiconductor chip packages include fan-out type WLP, fan-in type WLP, fan-out type PLP, and fan-in type PLP. The sheet-like laminate material can also be used, for example, to form an insulating layer of a circuit board (resin sheet for insulating layer of a circuit board). Furthermore, the sheet-like laminate material may be used as a material for a MUF used after connecting a semiconductor chip to a board. In particular, the sheet-like laminate material is suitable for forming an interlayer insulating layer.
[0161] [Circuit board] A circuit board according to one embodiment of the present invention includes a cured product of a resin composition. Typically, the circuit board includes an insulating layer formed of the cured product of the resin composition. The insulating layer includes the cured product of the above-mentioned resin composition, and preferably includes only the cured product of the above-mentioned resin composition. This circuit board can be manufactured, for example, by a manufacturing method including the following steps (I) and (II). (I) A step of forming a resin composition layer on an inner layer substrate. (II) A step of curing the resin composition layer to form an insulating layer.
[0162] The "inner layer substrate" used in step (I) is a member that serves as the base material of a circuit board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The substrate may have a conductor layer on one or both sides, and the conductor layer may be patterned. An inner layer substrate having a conductor layer (circuit) formed on one or both sides of the substrate may be called an "inner layer circuit substrate". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be further formed during the manufacture of a circuit substrate is also included in the above-mentioned "inner layer substrate". When the circuit substrate is a circuit board with built-in components, an inner layer substrate with built-in components may be used.
[0163] When the conductor layer of the inner layer substrate is patterned, the minimum line / space ratio of the conductor layer is preferably small in order to utilize the advantage of excellent crack resistance. "Line" refers to the wiring width of the conductor layer, and "space" refers to the gap width between the wirings. The range of the minimum line / space ratio is preferably 100 / 100 μm or less (i.e., pitch is 200 μm or less), more preferably 50 / 50 μm or less, even more preferably 30 / 30 μm or less, even more preferably 20 / 20 μm or less, and even more preferably 10 / 10 μm or less. The lower limit may be, for example, 0.5 / 0.5 μm or more. The pitch may be uniform or non-uniform throughout the conductor layer. The minimum pitch of the conductor layer may be, for example, 100 μm or less, 60 μm or less, 40 μm or less, 36 μm or less, or 30 μm or less.
[0164] The resin composition layer can be formed on the inner layer substrate by, for example, laminating the inner layer substrate and the resin sheet. The inner layer substrate and the resin sheet can be laminated by, for example, thermocompression bonding the resin sheet to the inner layer substrate from the support side. Examples of the member for thermocompression bonding the resin sheet to the inner layer substrate (hereinafter also referred to as the "thermocompression bonding member") include a heated metal plate (such as a SUS plate) or a metal roll (such as a SUS roll). It is preferable to press the thermocompression bonding member through an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the inner layer substrate, rather than directly pressing the resin sheet with the thermocompression bonding member.
[0165] The lamination of the inner layer substrate and the resin sheet may be performed by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination is preferably performed under reduced pressure conditions of 26.7hPa or less.
[0166] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.
[0167] After lamination, the laminated resin sheet may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the support side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.
[0168] The support may be removed between step (I) and step (II) or after step (II).
[0169] In step (II), the resin composition layer is cured to form an insulating layer made of a cured product of the resin composition. The resin composition layer is usually cured by thermal curing. Specific curing conditions for the resin composition layer may vary depending on the type of resin composition. In one example, the curing temperature is preferably 120°C to 240°C, more preferably 150°C to 220°C, and even more preferably 170°C to 210°C. The curing time may be preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.
[0170] The method for producing a circuit board preferably includes preheating the resin composition layer at a temperature lower than the curing temperature before the thermal curing of the resin composition layer. For example, prior to thermal curing of the resin composition layer, the resin composition layer may be preheated at a temperature of usually 50° C. to 150° C., preferably 60° C. to 140° C., more preferably 70° C. to 130° C. for usually 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.
[0171] In producing a circuit board, the steps of (III) drilling holes in the insulating layer, (IV) roughening the insulating layer, and (V) forming a conductor layer may be further carried out. These steps (III) to (V) may be carried out according to various methods known to those skilled in the art for use in producing circuit boards. When the support is removed after step (II), the support may be removed between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V). If necessary, the steps (I) to (V) of forming the insulating layer and the conductor layer may be repeated to produce a circuit board having a multilayer structure such as a multilayer printed wiring board.
[0172] In another embodiment, the circuit board can be manufactured using the above-mentioned prepreg. The manufacturing method can be basically the same as when a resin sheet is used.
[0173] Step (III) is a step of drilling holes in the insulating layer, which allows holes such as via holes and through holes to be formed in the insulating layer. Step (III) may be performed using, for example, a drill, a laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The size and shape of the hole may be appropriately determined depending on the design of the circuit board.
[0174] Step (IV) is a step of roughening the insulating layer. Usually, in this step (IV), smears are also removed. Therefore, the roughening treatment is sometimes called "desmear treatment". The procedure and conditions of the roughening treatment are not particularly limited, and known procedures and conditions that are usually used when forming an insulating layer of a circuit board can be adopted. For example, the insulating layer can be roughened by performing a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order.
[0175] Examples of the swelling liquid used in the roughening treatment include an alkaline solution and a surfactant solution, and an alkaline solution is preferred. As the alkaline solution, a sodium hydroxide solution and a potassium hydroxide solution are more preferred. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment using a swelling liquid can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferred to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 to 15 minutes.
[0176] An example of an oxidizing agent used in the roughening treatment is an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 minutes to 30 minutes. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan.
[0177] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and a commercially available product is, for example, "Reduction Solution Securigant P" manufactured by Atotech Japan. Treatment with a neutralizing solution can be performed by immersing the surface that has been roughened with an oxidizing agent in a neutralizing solution at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the object that has been roughened with an oxidizing agent is immersed in a neutralizing solution at 40°C to 70°C for 5 to 20 minutes is preferred.
[0178] Step (V) is a step of forming a conductor layer, and the conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among these, from the viewpoints of versatility in forming the conductor layer, cost, ease of patterning, and the like, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred.
[0179] The conductor layer may be a single-layer structure, or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. When the conductor layer has a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.
[0180] The thickness of the conductor layer depends on the desired design of the circuit board, but is generally 3 μm to 35 μm, and preferably 5 μm to 30 μm.
[0181] In one embodiment, the conductor layer may be formed by plating. For example, a conductor layer having a desired wiring pattern can be formed by plating the surface of the insulating layer by a conventionally known technique such as a semi-additive method or a full-additive method. From the viewpoint of ease of production, the semi-additive method is preferred. Below, an example of forming the conductor layer by the semi-additive method is shown.
[0182] First, a plating seed layer is formed on the surface of an insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer having a desired wiring pattern.
[0183] In another embodiment, the conductor layer may be formed using a metal foil. When the conductor layer is formed using a metal foil, it is preferable to carry out step (V) between steps (I) and (II). For example, after step (I), the support is removed, and a metal foil is laminated on the exposed surface of the resin composition layer. The lamination of the resin composition layer and the metal foil may be carried out by a vacuum lamination method. The lamination conditions may be the same as those described for step (I). Next, step (II) is carried out to form an insulating layer. Thereafter, a conductor layer having a desired wiring pattern can be formed by a conventionally known technique such as a subtractive method or a modified semi-additive method, using the metal foil on the insulating layer.
[0184] The metal foil can be produced by a known method such as an electrolytic method, a rolling method, etc. Commercially available metal foils include, for example, HLP foil and JXUT-III foil manufactured by JX Nippon Mining & Metals Corporation, and 3EC-III foil and TP-III foil manufactured by Mitsui Mining & Smelting Co., Ltd.
[0185] [Semiconductor chip package] A semiconductor chip package according to an embodiment of the present invention includes a cured resin composition. Typically, the semiconductor chip package includes an insulating layer formed of the cured resin composition. The insulating layer includes the cured resin composition described above, and preferably includes only the cured resin composition described above. Examples of this semiconductor chip package include the following.
[0186] The semiconductor chip package according to the first example includes the above-mentioned circuit board and a semiconductor chip mounted on the circuit board. This semiconductor chip package can be manufactured by bonding the semiconductor chip to the circuit board.
[0187] The bonding conditions between the circuit board and the semiconductor chip may be any conditions that allow conductive connection between the terminal electrodes of the semiconductor chip and the circuit wiring of the circuit board. For example, the conditions used in flip-chip mounting of the semiconductor chip may be used. Also, for example, the semiconductor chip and the circuit board may be bonded via an insulating adhesive.
[0188] An example of a bonding method is a method of bonding a semiconductor chip to a circuit board. The bonding conditions are that the bonding temperature is usually in the range of 120°C to 240°C (preferably in the range of 130°C to 200°C, more preferably in the range of 140°C to 180°C), and the bonding time is usually in the range of 1 second to 60 seconds (preferably in the range of 5 seconds to 30 seconds).
[0189] Another example of the bonding method is a method of bonding a semiconductor chip to a circuit board by reflow. The reflow conditions may be in the range of 120°C to 300°C.
[0190] After the semiconductor chip is bonded to the circuit board, the semiconductor chip may be filled with a molded underfill material, which may be the resin composition described above.
[0191] The semiconductor chip package according to the second example includes a semiconductor chip and an insulating layer formed of a cured product of a resin composition. Examples of the semiconductor chip package according to the second example include a fan-out type WLP and a fan-out type PLP.
[0192] Fig. 1 is a cross-sectional view showing a fan-out type WLP as an example of a semiconductor chip package according to an embodiment of the present invention. A semiconductor chip package 100 as a fan-out type WLP includes, for example, a semiconductor chip 110, a sealing layer 120 formed to cover the periphery of the semiconductor chip 110, a rewiring formation layer 130 as an insulating layer provided on the surface of the semiconductor chip 110 opposite to the sealing layer 120, a rewiring layer 140 as a conductor layer, a solder resist layer 150, and bumps 160, as shown in Fig. 1.
[0193] The method for manufacturing such a semiconductor chip package includes: (i) laminating a temporary fixing film onto a substrate; (ii) a step of temporarily fixing a semiconductor chip on a temporary fixing film; (iii) forming an encapsulation layer on the semiconductor chip; (iv) peeling the substrate and the temporary fixing film from the semiconductor chip; (v) forming a rewiring formation layer on the surface from which the substrate and the temporary fixing film of the semiconductor chip have been peeled off; (vi) forming a redistribution layer as a conductor layer on the redistribution layer; and (vii) forming a solder resist layer on the rewiring layer; The method for manufacturing the semiconductor chip package further comprises: (viii) dicing the plurality of semiconductor chip packages into individual semiconductor chip packages; may also include
[0194] (Step (i)) Step (i) is a step of laminating a temporary fixing film on a substrate. The lamination conditions for the substrate and the temporary fixing film can be the same as the lamination conditions for the inner layer substrate and the resin sheet in the method for producing a circuit board.
[0195] Examples of the substrate include silicon wafers; glass wafers; glass substrates; metal substrates such as copper, titanium, stainless steel, and cold-rolled steel (SPCC); substrates such as FR-4 substrates in which glass fibers are impregnated with epoxy resin or the like and then heat-cured; and substrates made of bismaleimide triazine resins such as BT resin.
[0196] The temporary fixing film may be made of any material that can be peeled off from the semiconductor chip and can temporarily fix the semiconductor chip. Commercially available products include "Riva Alpha" manufactured by Nitto Denko Corporation.
[0197] (Step (ii)) Step (ii) is a step of temporarily fixing the semiconductor chip on the temporary fixing film. The temporary fixing of the semiconductor chip can be performed using, for example, a device such as a flip chip bonder or a die bonder. The layout and number of the semiconductor chips can be appropriately set depending on the shape and size of the temporary fixing film, the number of semiconductor chip packages to be produced, etc. For example, the semiconductor chips may be temporarily fixed by arranging them in a matrix shape of multiple rows and multiple columns.
[0198] (Step (iii)) Step (iii) is a step of forming an encapsulating layer on the semiconductor chip. The encapsulating layer can be formed, for example, from a photosensitive resin composition or a thermosetting resin composition. This encapsulating layer may be formed from a cured product of the resin composition according to the above-mentioned embodiment. The encapsulating layer can usually be formed by a method including a step of forming a resin composition layer on the semiconductor chip and a step of curing this resin composition layer to form the encapsulating layer.
[0199] (Step (iv)) Step (iv) is a step of peeling off the substrate and the temporary fixing film from the semiconductor chip. It is desirable to adopt an appropriate peeling method according to the material of the temporary fixing film. For example, the peeling method may be a method of heating, foaming or expanding the temporary fixing film to peel it off. In addition, for example, the peeling method may be a method of irradiating the temporary fixing film with ultraviolet light through the substrate to reduce the adhesive strength of the temporary fixing film to peel it off.
[0200] When the base material and the temporary fixing film are peeled off from the semiconductor chip as described above, the surface of the encapsulating layer is exposed. The manufacturing method of the semiconductor chip package may include polishing the exposed surface of the encapsulating layer. By polishing, the smoothness of the surface of the encapsulating layer can be improved.
[0201] (Process (v)) Step (v) is a step of forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the base material and the temporary fixing film are peeled off. Usually, this rewiring formation layer is formed on the semiconductor chip and the sealing layer. The rewiring formation layer can be formed by a cured product of the resin composition according to the above-mentioned embodiment. Usually, the rewiring formation layer can be formed by a method including a step of forming a resin composition layer on the semiconductor chip and a step of curing the resin composition layer to form the rewiring formation layer. The formation of the resin composition layer on the semiconductor chip can be performed by the same method as the method of forming the resin composition layer on the inner layer substrate described in the above-mentioned method for producing a circuit board, except that a semiconductor chip is used instead of the inner layer substrate.
[0202] After forming a resin composition layer on a semiconductor chip, the resin composition layer is cured to obtain a rewiring formation layer as an insulating layer containing a cured product of the resin composition. The curing conditions of the resin composition layer may be the same as the curing conditions of the resin composition layer in the manufacturing method of a circuit board. When the resin composition layer is thermally cured, the resin composition layer may be subjected to a preheating treatment in which the resin composition layer is heated at a temperature lower than the curing temperature before the thermal curing. The treatment conditions of this preheating treatment may be the same as the preheating treatment in the manufacturing method of a circuit board. Usually, after forming the rewiring formation layer, holes are formed in the rewiring formation layer to connect the semiconductor chip and the rewiring layer.
[0203] (Step (vi)) Step (vi) is a step of forming a redistribution layer as a conductor layer on the redistribution formation layer. The method of forming the redistribution layer on the redistribution formation layer may be the same as the method of forming a conductor layer on an insulating layer in the method of manufacturing a circuit board. Steps (v) and (vi) may be repeated to alternately stack the redistribution layer and the redistribution formation layer (build up).
[0204] (Step (vii)) Step (vii) is a step of forming a solder resist layer on the rewiring layer. The material of the solder resist layer can be any material having insulating properties. Among them, from the viewpoint of ease of manufacturing the semiconductor chip package, a photosensitive resin composition and a thermosetting resin composition are preferred. The solder resist layer may be formed by a cured product of the resin composition according to the above-mentioned embodiment.
[0205] In step (vii), bumping may be performed to form bumps, if necessary. The bumping may be performed by a method such as solder balls or solder plating. In the bumping, via holes may be formed in the same manner as in step (v).
[0206] (Step (viii)) The method for producing a semiconductor chip package may include a step (viii) in addition to the steps (i) to (vii). The step (viii) is a step of dicing a plurality of semiconductor chip packages into individual semiconductor chip packages to separate them. The method for dicing the semiconductor chip packages into individual semiconductor chip packages is not particularly limited.
[0207] [Semiconductor Devices] The semiconductor device includes the above-mentioned circuit board or semiconductor chip package. Examples of the semiconductor device include various semiconductor devices used in electrical products (e.g., computers, mobile phones, smartphones, tablet devices, wearable devices, digital cameras, medical devices, televisions, etc.) and vehicles (e.g., motorcycles, automobiles, trains, ships, aircraft, etc.). EXAMPLES
[0208] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the following examples. In the following description, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Unless otherwise specified, the temperature and pressure conditions were room temperature (25°C) and atmospheric pressure (1 atm). In the following description, "L / S" represents the line (wiring width) / space (gap width) ratio of the conductor pattern.
[0209] <Example 1> 25 parts of biphenyl-type solid epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent approximately 269 g / eq.), 15 parts of naphthalene-type solid epoxy resin ("ESN475V" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent approximately 332 g / eq.), 5 parts of trimethylolpropane-type liquid epoxy resin ("ED-505" manufactured by Adeka Corporation, epoxy equivalent approximately 150 g / eq., 150 mPa s) were added to 70 parts of methyl ethyl ketone (MEK), and the mixture was heated and dissolved with stirring to obtain a solution. This solution was cooled to room temperature to prepare a dissolved composition of the epoxy resin.
[0210] To this dissolved composition, 5 parts of a triazine skeleton-containing phenolic hardener (DIC Corporation's "LA-3018-50P", active group equivalent of about 151 g / eq., 2-methoxypropanol solution with a non-volatile content of 50%), 26 parts of an active ester compound (DIC Corporation's "HPC-8000-65T", active ester group equivalent of about 223 g / eq., toluene solution with a non-volatile content of 65%), and 10 parts of a phenoxy resin (Mitsubishi Chemical Corporation's "YX7553BH30", non-volatile content of 30%) were added. A resin varnish was prepared by mixing 8 parts of a 1:1 solution of 5% by mass of MEK and cyclohexanone, 180 parts of biomass silica (MIT's "Ethical Silica", average particle size 3.7 μm, carbon content 0.6% by mass) that had been surface-treated with a silane coupling agent (Shin-Etsu Chemical's "KBM-573"), and 4 parts of an amine-based curing accelerator (4-dimethylaminopyridine (DMAP), MEK solution with 5% by mass of non-volatile components) and dispersing the mixture uniformly using a high-speed rotating mixer.
[0211] A polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm) that had been subjected to a release treatment was prepared as a support. A resin varnish was uniformly applied to the release surface (the surface that had been subjected to the release treatment) of this support so that the thickness of the resin composition layer was 40 μm, and the resin varnish was dried at 80° C. to 120° C. (average 100° C.) for 5 minutes to produce a resin sheet including a support and a resin composition layer.
[0212] <Example 2> In Example 1, the amount of triazine skeleton-containing phenolic curing agent (DIC Corporation's "LA-3018-50P", active group equivalent of about 151 g / eq., 2-methoxypropanol solution with non-volatile content of 50%) was changed from 5 parts to 12 parts. In addition, 26 parts of active ester compound (DIC Corporation's "HPC-8000-65T", active ester group equivalent of about 223 g / eq., toluene solution with non-volatile content of 65%) was changed to 12 parts of naphthol-type curing agent (Nippon Steel Chemical & Material Corporation's "SN-485", hydroxyl group equivalent of about 205 g / eq.). A resin varnish and a resin sheet were produced in the same manner as in Example 1 except for the above items.
[0213] <Example 3> A resin varnish and a resin sheet were produced in the same manner as in Example 1, except that 5 parts of a carbodiimide-based curing agent (Nisshinbo Chemical Co., Ltd.'s "V-03", active group equivalent of approximately 216 g / eq., toluene solution with a non-volatile content of 50%) was added to the resin composition.
[0214] <Example 4> In Example 1, 5 parts of a triazine skeleton-containing phenolic curing agent (DIC Corporation's "LA-3018-50P", active group equivalent of about 151 g / eq., 2-methoxypropanol solution with non-volatile content of 50%) were not used. In addition, the amount of an active ester compound (DIC Corporation's "HPC-8000-65T", active ester group equivalent of about 223 g / eq., toluene solution with non-volatile content of 65%) was changed from 26 parts to 20 parts. In addition, 15 parts of a bisphenol A dicyanate prepolymer (Lonza Japan's "BA230S75", cyanate equivalent of about 232 g / eq., MEK solution with non-volatile content of 75% by mass) and 1 part of a 1% by mass MEK solution of cobalt (III) acetylacetonate (Tokyo Chemical Industry Co., Ltd.) were added to the resin composition. In addition, the amount of biomass silica (MIT's "Ethical Silica", average particle size 3.7 μm, carbon content 0.6% by mass) surface-treated with a silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573") was changed from 180 parts to 150 parts. A resin varnish and a resin sheet were produced in the same manner as in Example 1, except for the above.
[0215] <Example 5> In Example 1, 5 parts of trimethylolpropane type liquid epoxy resin (ADEKA CORPORATION "ED-505", epoxy equivalent of about 150 g / eq., 150 mPa s) was changed to 5 parts of neopentyl glycol type liquid epoxy resin (ADEKA CORPORATION "ED-523T", epoxy equivalent of about 140 g / eq., 15 mPa s). In addition, the amount of biomass silica (MIT Corporation "Ethical Silica", average particle size 3.7 μm, carbon content 0.6% by mass) surface-treated with a silane coupling agent (Shin-Etsu Chemical Co., Ltd. "KBM-573") was changed from 180 parts to 60 parts. Furthermore, 5 parts of vinylbenzyl-modified polyphenylene ether ("OPE-2St 2200" manufactured by Mitsubishi Gas Chemical Co., Ltd., toluene solution with non-volatile content of 65%) and 120 parts of spherical silica ("SO-C2" manufactured by Admatechs Co., Ltd., average particle size 0.5 μm, carbon content 0%, biomass ratio 0%) surface-treated with a silane coupling agent ("KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd.) were added to the resin composition. A resin varnish and a resin sheet were produced in the same manner as in Example 1 except for the above items.
[0216] <Example 6> Biphenyl type epoxy resin (Nippon Kayaku "NC3000L", epoxy equivalent approx. 269g / eq.) 10 parts, bisphenol type liquid epoxy resin (Nippon Steel Chemical & Material "ZX1059", 1:1 mixture of bisphenol A type and bisphenol F type, epoxy equivalent approx. 169g / eq., 2600mPa s) 5 parts, naphthylene ether type solid epoxy resin (DIC "HP-6000" 70 parts of methyl ethyl ketone was added to 20 parts of a dicyclopentadiene-type solid epoxy resin ("HP7200HH" manufactured by DIC Corporation, epoxy equivalent approximately 283 g / eq.), and 5 parts of a trimethylolpropane-type liquid epoxy resin ("ED-505" manufactured by ADEKA Corporation, epoxy equivalent approximately 150 g / eq., 150 mPa s), and the mixture was heated and dissolved with stirring to obtain a solution. This solution was cooled to room temperature to prepare a dissolved composition of the epoxy resin.
[0217] To this dissolved composition, 5 parts of a triazine skeleton-containing phenolic hardener (DIC Corporation's "LA-3018-50P", active group equivalent of about 151 g / eq., 2-methoxypropanol solution with a non-volatile content of 50%), 24 parts of an active ester compound (DIC Corporation's "EXB9416-70BK", active ester group equivalent of about 330 g / eq., methyl isobutyl ketone solution with a non-volatile content of 70%), 3 parts of a biphenyl aralkyl novolac type maleimide (Nippon Kayaku Co., Ltd.'s "MIR-3000-70MT", MEK / toluene mixed solution with a non-volatile content of 70%), phenoxy resin Eight parts of "YX7553BH30" manufactured by Mitsubishi Chemical Corporation, a 1:1 solution of MEK and cyclohexanone with a non-volatile content of 30% by mass, 180 parts of biomass silica ("Ethical Silica" manufactured by MIT, average particle size 3.7 μm, carbon content 0.6% by mass) that had been surface-treated with a silane coupling agent ("KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd.), and four parts of an imidazole-based curing accelerator ("1B2PZ" manufactured by Shikoku Kasei Co., Ltd., 1-benzyl-2-phenylimidazole, MEK solution with a non-volatile content of 10% by mass) were mixed and uniformly dispersed using a high-speed rotating mixer to prepare a resin varnish.
[0218] A polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm) that had been subjected to a release treatment was prepared as a support. A resin varnish was uniformly applied to the release surface (the surface that had been subjected to the release treatment) of this support so that the thickness of the resin composition layer was 40 μm, and the resin varnish was dried at 80° C. to 120° C. (average 100° C.) for 5 minutes to produce a resin sheet including a support and a resin composition layer.
[0219] <Example 7> A resin varnish and a resin sheet were produced in the same manner as in Example 1, except that 5 parts of a trimethylolpropane type liquid epoxy resin ("ED-505" manufactured by ADEKA CORPORATION, epoxy equivalent of about 150 g / eq., 150 mPa s) was changed to 5 parts of a bisphenol A type liquid epoxy resin ("828EL" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent of about 180 g / eq., 13,000 mPa s).
[0220] <Example 8> In Example 1, the amount of trimethylolpropane type liquid epoxy resin ("ED-505" manufactured by Adeka Corporation, epoxy equivalent approximately 150 g / eq., 150 mPa s) was changed from 5 parts to 2 parts. In addition, 3 parts of bixylenol type solid epoxy resin (epoxy equivalent 190 g / eq., "YX4000HK" manufactured by Mitsubishi Chemical Corporation) was added to the resin composition. Apart from the above, a resin varnish and a resin sheet were produced in the same manner as in Example 1.
[0221] <Comparative Example 1> In Example 1, 5 parts of trimethylolpropane type liquid epoxy resin ("ED-505" manufactured by ADEKA CORPORATION, epoxy equivalent of approximately 150 g / eq., 150 mPa s) was not used. In addition, the amount of naphthalene type solid epoxy resin ("ESN475V" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent of approximately 332 g / eq.) was changed from 15 parts to 20 parts. Apart from the above, a resin varnish and a resin sheet were produced in the same manner as in Example 1.
[0222] <Comparative Example 2> In Example 1, 180 parts of biomass silica (MIT's "Ethical Silica", average particle size 3.7 μm, carbon content 0.6% by mass) surface-treated with a silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573") was changed to 180 parts of spherical silica (Admatechs' "SO-C2", average particle size 0.5 μm, biomass ratio 0%) surface-treated with a silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573"). A resin varnish and a resin sheet were produced in the same manner as in Example 1, except that the amount of the biomass silica (MIT's "Ethical Silica", average particle size 3.7 μm, carbon content 0.6% by mass) surface-treated with a silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573") was changed to 180 parts.
[0223] <Comparative Example 3> In Comparative Example 2, a resin varnish and a resin sheet were produced in the same manner as in Comparative Example 2, except that 5 parts of an ion scavenger (manufactured by Toa Gosei Co., Ltd., "IXEPLAS-A3", a mixture of hydrotalcite and zirconium phosphate) was added to the resin composition.
[0224] <Comparative Example 4> In Comparative Example 2, the amount of biphenyl-type solid epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent approximately 269 g / eq.) was changed from 25 parts to 20 parts. In addition, 5 parts of black pigment dispersion ("NV-7-201" manufactured by Nippon Pigment Co., Ltd., liquid bisphenol F-type epoxy resin containing carbon black, carbon black amount 25%) was added to the resin composition. Apart from the above, a resin varnish and a resin sheet were produced in the same manner as in Comparative Example 2.
[0225] <Measurement of epoxy resin viscosity> The viscosity of the liquid epoxy resin was measured using an E-type viscometer (Toki Sangyo "RE-25U" using a 1° 34' × R24 cone rotor) at 25°C and 20 rpm.
[0226] <Test Example 1: Measurement of glass transition temperature and linear thermal expansion coefficient of cured product> (1) Preparation of cured material for evaluation: A PET film ("501010" manufactured by Lintec Corporation, thickness 50 μm, 240 mm square) having a release-treated surface and an untreated surface that was not release-treated was prepared. A glass cloth-based epoxy resin double-sided copper-clad laminate ("R5715ES" manufactured by Panasonic Corporation, thickness 0.7 mm, 255 mm square) was placed on the untreated surface of this PET film, and the four sides were fixed with polyimide adhesive tape (width 10 mm).
[0227] The resin varnish produced in the examples and comparative examples was applied to the treated surface of the PET film using a die coater so that the thickness of the resin composition layer after drying was 40 μm, and then dried at 80° C. to 120° C. (average 100° C.) for 10 minutes to obtain a resin sheet. Next, after being placed in an oven at 190° C., the resin composition layer was thermally cured under curing conditions of 90 minutes. After thermal curing, the polyimide adhesive tape was peeled off, the glass cloth-based epoxy resin double-sided copper-clad laminate was removed, and the PET film was further peeled off to obtain a sheet-like cured product. The obtained cured product is referred to as the "cured product for evaluation".
[0228] (2) Measurement of glass transition temperature and linear thermal expansion coefficient: The cured product for evaluation was cut to obtain a test piece with a width of about 5 mm and a length of about 15 mm. This test piece was subjected to a thermomechanical analysis by a tensile load method using a thermomechanical analyzer (Rigaku Corporation's "Thermo Plus TMA8310"). In detail, after mounting the test piece on the thermomechanical analyzer, measurements were performed twice consecutively under the measurement conditions of a load of 1 g and a heating rate of 5°C / min. Then, in the second measurement, the glass transition temperature Tg (°C) and the average linear thermal expansion coefficient CTE (ppm / °C) in the range from 25°C to 150°C were calculated.
[0229] <Test Example 2: Measurement of minimum melt viscosity of resin composition> The melt viscosity of the resin composition contained in the resin composition layer of the resin sheet produced in the examples and comparative examples was measured using a dynamic viscoelasticity measuring device (UBM's "Rheosol-G3000"). This measurement was performed on a 1 g sample taken from the resin composition layer using parallel plates with a diameter of 18 mm. The measurement conditions were a starting temperature of 60°C to 200°C, a heating rate of 5°C / min, a measurement temperature interval of 2.5°C, and a vibration of 1 Hz / deg. The minimum melt viscosity was determined from the measured values of the melt viscosity obtained.
[0230] <Test Example 3: Undulation Measurement> The resin sheets produced in the examples and comparative examples were laminated on a conductor layer (thickness 35 μm, L / S=160 μm / 160 μm) formed in a comb-tooth pattern using a batch-type vacuum pressure laminator ("MVLP-500" manufactured by Meiki Co., Ltd.). The lamination was performed by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing for 30 seconds at 100°C and a pressure of 0.74 MPa. After lamination, the PET film as a support was peeled off, and the resin composition was cured under the curing conditions of 100°C for 30 minutes and then 180°C for 30 minutes to form an insulating layer.
[0231] The difference between the surface height of the insulating layer on the conductor layer and the surface height of the insulating layer other than the conductor layer was determined as the undulation Rt of the insulating layer. The undulation Rt of the insulating layer was measured as the maximum peak-to-valley value using a non-contact surface roughness meter (Beeco Instruments' "WYKO NT3300") in VSI mode with a 10x lens and a measurement range of 1.2mm x 0.91mm. The undulation Rt of 2.0μm or less was evaluated as "good", the undulation Rt of 2.0μm to 3.0μm was evaluated as "△", and the undulation Rt of more than 3.0μm was evaluated as "x".
[0232] <Test Example 4: Evaluation of insulation reliability> A polyimide film was prepared on which a comb-shaped electrode (L / S=15 μm / 15 μm) was formed by a copper circuit on the surface. The resin sheets produced in the examples and comparative examples were laminated to the polyimide film using a batch-type vacuum pressure laminator ("MVLP-500" manufactured by Meiki Co., Ltd.) so that the resin composition layer of the resin sheet was in contact with the copper circuit surface. The lamination was performed by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing for 30 seconds at 100°C and a pressure of 0.74 MPa. After peeling off the PET film as a support, the resin composition layer was thermally cured at 190°C for 90 minutes to obtain a sample laminate for evaluating insulation reliability.
[0233] The sample laminate was placed in a highly accelerated life tester (Kusumoto Chemical Industries, Ltd., "PM422") and left for 100 hours under conditions of 130°C and 85% RH with a voltage of 3.3 V applied. After that, the insulation resistance value of the sample laminate was measured. The insulation resistance value was 1.0×10 9 Ω or more is marked as "○", 1.0×10 8 Ω or more 1.0×10 9 If it is less than Ω, it is marked as "△", and if it is less than 1.0×10 8 The case where it was less than Ω was evaluated as "X".
[0234] <Test Example 5: Evaluation of reflow resistance> (1) Preparation of the inner layer board: A glass cloth-based epoxy resin double-sided copper-clad laminate with copper foil on the surface (copper foil thickness 18 μm, substrate thickness 0.8 mm, Panasonic "R1515A") was prepared. The copper foil on the surface of this inner layer substrate was etched with a microetching agent (Mec "CZ8101") to a copper etching amount of 1 μm, and roughening treatment was performed. After that, it was dried at 190 ° C for 30 minutes to prepare a surface-treated inner layer substrate.
[0235] (2) Lamination and curing of resin sheets: The resin sheets produced in the examples and comparative examples were laminated on both sides of the substrate-treated inner layer substrate using a batch-type vacuum pressure laminator (a two-stage build-up laminator "CVP700" manufactured by Nikko Materials Co., Ltd.) so that the resin composition layer was bonded to the substrate-treated inner layer substrate. This lamination was performed by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing at a temperature of 100°C and a pressure of 0.74 MPa for 30 seconds. The laminated resin sheet was then heat-pressed for 60 seconds at atmospheric pressure, 100°C, and a pressure of 0.5 MPa to smooth it. This was then placed in an oven at 130°C and heated for 30 minutes, and then transferred to an oven at 170°C and heated for 30 minutes to thermally cure the resin composition layer, thereby obtaining an intermediate substrate having a layer structure of support / insulating layer / substrate-treated inner layer substrate / insulating layer / support.
[0236] (3) Conductor formation by plating: The support was peeled off from the intermediate substrate. The intermediate substrate was then immersed in a swelling liquid (Swelling Dip Securigant P, manufactured by Atotech Japan) at 60°C for 10 minutes. Next, the intermediate substrate was immersed in a roughening liquid (Concentrate Compact P, manufactured by Atotech Japan; KMnO 4 The intermediate substrate was immersed in a neutralizing solution (Reduction Solution Securigant P manufactured by Atotech Japan) at 40°C for 5 minutes.
[0237] Next, the intermediate substrate was 2The intermediate substrate was immersed in an electroless plating solution containing 1,2-dichlorophenyl ether at 40° C. for 5 minutes, and then immersed in an electroless copper plating solution at 25° C. for 20 minutes. After an annealing treatment was performed by heating at 150° C. for 30 minutes, the intermediate substrate was further subjected to copper sulfate electroplating to form a conductor layer with a thickness of 30 μm. Next, an annealing treatment was performed at 190° C. for 60 minutes to obtain a substrate for evaluating reflow resistance.
[0238] (4) Reflow resistance evaluation: The reflow resistance evaluation board was cut into small pieces of 100mm x 50mm, and passed through a reflow device ("HAS-6116" manufactured by Nippon Antom Co., Ltd.) that reproduces a solder reflow temperature of a peak temperature of 260°C 10 times (the reflow temperature profile complies with IPC / JEDEC J-STD-020C). Evaluation was performed on two small pieces, and pieces with 5 or more abnormalities such as blisters were judged as "X", pieces with 1 to 4 abnormalities were judged as "△", and pieces with no abnormalities at all were rated as "○".
[0239] [result] The results of the above-mentioned Examples and Comparative Examples are shown in the table below.
[0240] [Table 1]
[0241] [Table 2] [Explanation of symbols]
[0242] 100 Semiconductor chip package 110 Semiconductor Chip 120 Sealing layer 130 Rewiring formation layer 140 Redistribution layer 150 Solder resist layer 160 Bump
Claims
1. A resin composition comprising (A) an epoxy resin and (B) an inorganic filler, (A) the epoxy resin comprises (A-1) a liquid epoxy resin; (B) the inorganic filler contains (B-1) a carbon-containing inorganic filler, (B-1) The carbon-containing inorganic filler is silica particles having a carbon content of 0.1% by mass or more and 5% by mass or less, The amount of the liquid epoxy resin (A-1) is 0.5% by mass or more based on 100% by mass of the non-volatile components of the resin composition; (B-1) A resin composition, in which the amount of a carbon-containing inorganic filler is 10% by mass or more based on 100% by mass of the non-volatile components of the resin composition.
2. The resin composition according to claim 1 , further comprising a curing agent (C).
3. The resin composition according to claim 1, wherein the amount of the carbon-containing inorganic filler (B-1) is 20 mass% or more relative to 100 mass% of the total amount of the inorganic filler (B).
4. The resin composition according to claim 1, wherein the carbon content of the carbon-containing inorganic filler (B-1) is 0.2 mass% or more.
5. The resin composition according to claim 1, wherein the liquid epoxy resin (A-1) has a weight average molecular weight of 1,000 or less.
6. The resin composition according to claim 1, wherein the liquid epoxy resin (A-1) is a non-aromatic epoxy resin.
7. The resin composition according to claim 1, wherein the liquid epoxy resin (A-1) has a viscosity of 15,000 mPa·s or less at 25°C.
8. The resin composition according to claim 1 , further comprising (D) a curing accelerator.
9. The resin composition according to claim 1 , further comprising a thermoplastic resin (E).
10. The resin composition of claim 1 having a minimum melt viscosity of less than 4,000 poise.
11. The resin composition was thermally cured at 190° C. for 90 minutes to obtain a cured product. When a voltage of 3.3 V was applied to the cured product for 100 hours in an environment of 130° C. and 85% RH, the insulation resistance value of the cured product measured using a comb-shaped electrode with a line / space of 15 μm / 15 μm was 1.0×10 8 The resin composition according to claim 1, having a modulus of elasticity of Ω or more.
12. The resin composition according to claim 1 , which is for forming an insulating layer.
13. A cured product of the resin composition according to any one of claims 1 to 12.
14. A sheet-like laminate material comprising the resin composition according to any one of claims 1 to 12.
15. A support and a resin composition layer formed on the support, A resin sheet, wherein the resin composition layer comprises the resin composition according to any one of claims 1 to 12.
16. A circuit board comprising a cured product of the resin composition according to any one of claims 1 to 12.
17. A semiconductor chip package comprising a cured product of the resin composition according to any one of claims 1 to 12.
18. A semiconductor device comprising the circuit board according to claim 16.
19. A semiconductor device comprising the semiconductor chip package according to claim 17.
Citation Information
Patent Citations
Epoxy resin composition for electric coil-casting
JP2002284962A
One-pack epoxy resin composition for semiconductor encapsulation, cured product, production method of semiconductor component, and semiconductor component
JP2016191031A
Method for manufacturing structure
JP2020037643A
Sheet type insulation varnish and method for manufacturing the same, electric apparatus and rotary electric machine
JP2021070748A
Method for producing aliphatic polyglycidyl ethers
JP3644761B2